Control of nanoscale forces on virus transport in porous media with surface heterogeneity - Bo Wan; Wenjing Zhang; Zhibing Yang; Rui Song; Yue Han; Shuxin Li (Water Research, 2027)

Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Stochastic neural dynamic modeling and analysis under environmental noise for exploring the production of K-complexes - Wenhua Wang; Jiangling Song; Wanrong Zan; Bo Wang; Yiming Li; Rui Zhang (Cognitive Neurodynamics, 2026)

Dual-scale flower detection and homography-guided cluster matching for robotic pollination in trellised kiwifruit orchards - Leilei He; Bo Jia; Juncai Huang; Rui Li; Spyros Fountas; Longsheng Fu (Biosystems Engineering, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

Accumulation of hydrophobic bile acids mediates chronic heat stress-induced liver-gut axis injury in spotted seabass (Lateolabrax maculatus) - Fan-bo Yang; Xue-shan Li; Kai Song; Ling Wang; Rui-juan Ma; Kang-le Lu; Chun-xiao Zhang (Aquaculture, 2026)

Aluminum mineral transformation drives reacidification and metal remobilization in a neutralized acidic pit lake - Junyi Gu; Lu Zhang; Ziyi Li; Rui Deng; Zijie Yu; Bo Wang; Zhengbo Yue; Jin Wang (Water Research, 2026)

Construction of spatiotemporal knowledge graph and case-based quantitative decision support for maritime search and rescue - Dongge Liu; Bo Ai; Liang Cheng; Rui Xie; Zhen Wen (Ocean Engineering, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Bioinspired ZIF-derived carbon architectures for corrosion-resistant broadband electromagnetic attenuation - Sihao Dou; Yutan Jiang; Yuxiang Zheng; Rui Gao; Zhiyuan Dan; Minghao Yang; Qiang Su; Dongdong Liu; Bo Zhong; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

FeCl3-catalyzed acetic acid pretreatment for surface-acetylated cellulose nanofibrils enabling Pickering emulsions and tunable optical composite films - Wei Liu; Xuan Wang; Rui Xu; Tairan Pang; Siyu Chen; Yuhan Liu; Ting Xu; Bo Pang; Haishun Du; Chuanling Si (Carbohydrate Polymers, 2026)

A dual-state emission NIR fluorescent sensor for intelligent dual-analyte detection and multisite imaging: From N2H4/ClO− and fingerprints to living cells and organisms - Su-qian Cai; Bo-wen An; Rui-yong Jiang; Shang-wei Yuan; Xin Xiao (Analytica Chimica Acta, 2026)

Situated Authenticity in South China Morning Tea: A Qualitative Comparison of Cantonese Yum Cha and Hainan Laobacha as Regional Food Practices - Futong Liu; Rui Wang; Bo Shu (International Journal of Gastronomy and Food Science, 2026)

Driving workload capacity of highway tunnel entrance and exit takeover under non-driving-related tasks: a multi-dimensional information coupling method - Shuangkai Zhu; Bo Liang; Jia An Niu; Rui Su; Haonan Long; Tao Deng; Mengdie Xu (Tunnelling and Underground Space Technology, 2026)

Thermo-mechanical damage characteristics and fracture behavior of backfill bodies in thermal energy storage cavities: An experimental and numerical study - Huicong Xu; Kai Li; Bo Zhang; Rui Zhan; Shangtong Yang; Xun Xi; Lianpeng Dai (Tunnelling and Underground Space Technology, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Ecological risk assessment of caffeine in global aquatic ecosystems: From land to sea - Bo Fan; Xiaolong Guo; Baoyi Zhao; Xinyue Zhang; Yanting Mao; Baokun Lei; Rui Xu; Yuhan Yang; Yunrui Li; Junlang Deng; Yishu Deng (Journal of Hazardous Materials, 2026)

Toxic effects and molecular mechanisms of Fluopyram on the liver of zebrafish (Danio rerio) - Yuqing Hou; Bo Cheng; Baihui Shi; Shuhan Li; Xuzhi Zhang; Lanjun Wang; Rui Yang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

Effects of interlayer cations and hydration on PFAS adsorption and mobility in montmorillonite: A molecular dynamics study - Chuncao Zhou; Rui Xu; Fusheng Zha; Qiao Wang; Bo Kang (Journal of Contaminant Hydrology, 2026)

Instant health or long-term wellness? A lay belief perspective on AI vs. human recipe recommenders - Bo Shu; Yanlin Mei; Weirong Liu; Rui Wang (Food Quality and Preference, 2026)

Dietary ellagic acid improves glucose and lipid homeostasis with concurrent gut microbiota and serum metabolome remodeling in db/db mice - Rui-Bo Jia; Weipei Li; Pengru Yan; Chunxia Zhou; Zirui Huang; Mouming Zhao (Food Bioscience, 2026)

Recent advances in electromechanical coupling functional metamaterials - Han Yan; Yi Zhang; Wei Zhong Jiang; Xiao Ji; Rui Zhu; Jing Bo Sun; Yi Min Xie; Ken E. Evans; Xin Ren (Engineering Structures, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Pore-scale investigation of pore structure characteristics and their impact on thermo-hydraulic coupled transport in unsaturated bentonite: From fractal reconstruction to direct numerical simulation - Guangchang Yang; Xin Gong; Bo Zhang; Rui Zhou; Yang Liu; Bing Bai (Computers and Geotechnics, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Diversity and drivers of marine heatwaves in the Beibu Gulf of the South China Sea - Bo Zhang; Qiang Wang; Lili Zeng; Kunshan Li; Yi Xie; Rui Shi (Climate Dynamics, 2026)

Prediction of antibiotic resistance genes and resistance mechanisms of Pseudomonas syringae pv. actinidiae strain L211 based on whole-genome sequencing - Rui Yang; Dan-ni Chen; Shuai Yang; Lang-bo Yi; Qing-zhong Peng (Journal of Plant Pathology, 2026)

A new sesquiterpene from the leaves of Heritiera littoralis Dryand with nitric oxide inhibitory activity - Rui Pi; Xianglong Bo; Furong Wu; Meijing Tan; Shichao Ju; Xishan Huang; Yanjun Zhang (Natural Product Research, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Mapping and environmental control analysis of susceptibility to retrogressive thaw slumps in the central Qinghai Tibet Plateau - Ruikai Hong; Xu He; Jichao Lv; Bin Xiao; Age Shama; Zhihan Yang; Yunjie Yang; Bo Zhang; Dujuan Zhang; Rui Zhang (Remote Sensing Applications: Society and Environment, 2026)

Agency through comparison: Reference-point evaluations and rural environmental participation after mining-induced resettlement - Bo Hu; Rui Wang; Liuna Geng; Huizhu Wang (Journal of Rural Studies, 2026)

A BODIPY-based nanotheranostic suppresses osteosarcoma via dual photodynamic/photothermal action by disruption of YAP1/β-catenin Axis - Zhewen Deng; Mengyuan Zhang; Senqiang Zhu; Yunlong Zhang; Haitao Liao; Jiaqi Li; Peiyu Yan; Qi Zhang; Rui Liu; Bo Ma (Journal of Photochemistry and Photobiology B: Biology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Genetic discrimination of the Dongshan Pb-Zn-Cu deposit based on sphalerite chemistry - Yi-Chen Chen; Shi-Jiong Han; Cheng-Gang Cao; Jun-Wei Bo; Yu-Rui Yuan; Ming-Yu Tang; Jin-Xin Yuan (Journal of Geochemical Exploration, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

In vivo monitoring of the impact of microplastic particle size on the absorption and transport of Pyrethroids in Malabar spinach - Jiajia Han; Bo Zhu; Yuemei Chen; Rui Gao; Guosheng Chen; Junlang Qiu; Fang Zhu; Gangfeng Ouyang (Food Chemistry, 2026)

Experimental study on seismic behaviour of full-scale glued laminated timber frame-glass wall composite structural unit - Tian Xia; Tao Zhou; Rui Xu; Hao Huang; Shao-Bo Kang (Engineering Structures, 2026)

Effect of alkali and alkaline earth metals accumulation in process water on humic acids formation during the circulating hydrothermal carbonization of Chinese medicine residues - Xiaoyuan Zheng; Xudong Xing; Rui Wang; Zhi Ying; Bo Wang; Binlin Dou (Biomass and Bioenergy, 2026)

Pseudofrenelopsis (Cheirolepidiaceae) from the Lower Cretaceous of northwestern China and its paleoclimatic and biogeographic significances - Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Cretaceous Research, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

A polar strapdown airborne gravimetry method based on the transverse coordinate system - Chao-bo Yu; Shao-kun Cai; Mei-ping Wu; Zhi-ming Xiong; Rui-hang Yu; Bai-nan Yang (Applied Geophysics, 2026)

Post-accretionary crustal growth and recycling in the Central Asian Orogenic Belt: new insights from Early Permian Bole rhyolites and regional zircon Hf mapping - Bo Liu; Zhi-Hao Xie; Rui-Xin Zhou; Xin-Yi Cheng; Ya-Nan Gong (International Geology Review, 2026)

Classification of SARS-CoV-2 Variants Through the Epistatic Circos Plots with Convolutional Neural Networks - Bo Jing; Kai-Rui Zhang; Hong-Li Zeng; Erik Aurell (Journal of Molecular Evolution, 2026)
The COVID-19 pandemic has profoundly affected global health, driven by the remarkable transmissibility and mutational adaptability of the SARS-CoV-2 virus. Although five variants of concern, Alpha, Beta, Gamma, Delta, and Omicron, have been identified, the classification task in this study is formulated using four classes: Alpha, Delta, Omicron, and Else, reflecting the sequence availability and temporal coverage of the dataset. Here, we develop an integrative framework that combines direct coupling analysis (DCA), Circos-based visualization, and convolutional neural networks (CNNs) to characterize lineage-specific epistatic signatures from large-scale SARS-CoV-2 genomic sequences. DCA-inferred pairwise mutational couplings were transformed into Circos images, which were then used as inputs for CNN-based classification models. The proposed framework achieved robust variant classification, with the best-performing model reaching a weighted-average $$F_1\text {-score}$$ of $$98.68± 0.75%$$ and an AUC close to 1. Additional temporal holdout analyses showed that the framework retained reasonable predictive capability across evolutionary time, yielding a weighted-average $$F_1\text {-score}$$ of 87.85%.

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Generalized traverse task scheduling based on THRO algorithm for AUV with energy-constrained - Qixin Sha; Rui Nian; Jiaming Zhang; Xiaoting Xu; Yue Shen; Bo He (Ocean Engineering, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Melt percolation and channelized melt flow in Neo-Tethyan oceanic lithospheric mantle - Haitao Ma; Pengjie Cai; Huichao Rui; Rongzhong Bo; Osman Parlak; Dongyang Lian; Jingsui Yang (Lithos, 2026)

A dynamic pseudo-label driven dual-branch transformer framework for multi-scenario lake water body mapping - Kedi Fang; Bo Wang; Si Chen; Huaqi Gu; Rui Xia; Hai Liu (Journal of Hydrology, 2026)

Micro-nano biochar interfaces promote adsorption-reduction coupling to accelerate bioelectrodechlorination in groundwater - Zena Zhang; Miao Lv; Rui Wang; Bo Wang; Ruoyu Du; Yuxuan Lou; Chunlin Wang; Xiaodun Jiang; Hai Hou; Zhiling Li; Fan Chen (Journal of Hazardous Materials, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Effects of heat input on heat-affected zone of simultaneously welded cruciform fillet joints in Q550D and Q690D steels - Yize Gao; Xiao-Ling Zhao; Yan-Bo Wang; Rui Yan; Zhe Sun; Guo-Qiang Li (Engineering Structures, 2026)

Visible-light-driven N-CDs/Cu photocatalysis for CO2 valorization to selenylated vinyl oxazolidinones - Jun-Bo Wang; Jia-Tong Guo; Shu-Rui Wang; Bei Ruan; Zhan-Hui Zhang (Chemical Engineering Journal, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Construction of Green Fluorescent Protein-Tagged Aeromonas veronii for Understanding Its Pathogenicity in Rice-Field Eel (Monopterus albus) - Changtan Yang; Jiali Jin; Liyong Ye; Bo Liu; Huan Ye; Huamei Yue; Chuangju Li; Hanwen Yuan; Rui Ruan (Fishes, 2026)
The rice-field eel (Monopterus albus) is an important economic aquaculture species in China. Aeromonas veronii is one of the most common pathogens, which has a high infection and mortality rate in rice-field eel culture. In this study, a strain of A. veronii (AV-MA), isolated from the intestine of a diseased rice-field eel, was labelled with green fluorescent protein (GFP) using mini-Tn7-based systems. The growth curve and virulence of the GFP-labelled AV-MA (AV-MAGFP) strain showed no significant differences compared to AV-MA. After immersion infection with AV-MAGFP at 2.5 × 109 CFU/mL, bacterial loads in the liver, stomach, intestine, spleen, kidney, and heart tissues peaked within 1–6 h, and then declined gradually over time. AV-MAGFP infection remarkably increased intestinal malondialdehyde (MDA) content, superoxide dismutase (SOD) and catalase (CAT) activities. Levels of interleukin-8 (IL-8), interleukin-10 (IL-10), Tumor necrosis factor-α (TNF-α) and nuclear factor kappa-B repressing factor (nkrf) mRNAs fluctuated in the intestine after infection. In conclusion, this study demonstrated that GFP DNA was inserted into the chromosome of A. veronii using mini-Tn7 system for tracking its invasion pathway in vivo of rice-field eels, which provides a useful tool for further studying the pathogen–host interaction mechanisms between A. veronii and M. albus.

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Particle dynamics characteristics in a vertical pipe hydraulic conveying system under different feed concentrations - Fei Yan; Songtao Zhang; Zhiyin Yang; Rui Zhu; Bo Song; Jian Zhang (Ocean Engineering, 2026)

Metabolic insights into the Fe/Mn-biochar assisted anammox-comammox process: Synergistic electron-transfer and structural resilience under nitrite starvation - Xurui Zhu; Xiaonong Zhang; Luomiao Ji; Rui Zhao; Bo Gao; Wen Sun; Peng Wu (Journal of Environmental Chemical Engineering, 2026)

Accelerated peroxymonosulfate activation via internal electron migration within Co3O4/Bi2Fe4O9 for efficient phenol degradation - Bo Liu; Hangyu Shi; Yawei Wang; Rui Liu; Shuangshuang Zuo; Qianqian Nie; Lei Yang; Hesheng Yu (Journal of Environmental Sciences, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Study on the synergistic high-temperature corrosion mechanism of NH3-H2S on different water wall tube materials under a strongly reducing atmosphere in an ammonia-coal co-firing environment - Rui Ma; Guoqiang Bu; Tiantian An; Bo Wei; Qianjin Lin; Lijuan Chen; Shan Wang; Kunpeng Liu; Lijie Song (Fuel, 2026)

Effects of ammonia-coal Co-pyrolysis on coal pyrolysis products and the NO reduction characteristics of char - Bohao Wang; Chenxu Lv; Rui Ma; Bo Wei; Lijuan Chen; Jianjiang Wang; Shan Wang; Lijie Song; Guoqiang Bu (Fuel, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

Quantitative source apportionment of soil geochemical elements in a typical mountain-plain transition zone, northern China: the combined influence of geological background and anthropogenic activities - Huan Li; Yi-Xuan Zhang; Yang Yao; Qin-Rui Zhang; Bo Zhang; Yong-Wei Zhao; Bing Han; Guo-Li Yuan (Environmental Geochemistry and Health, 2026)

Linking soil nematode communities to plant- and microbial-derived carbon in a 15-year field experiment - Jigao Wang; Yanli Jing; Tao Wang; Kai Wei; Rui Yang; Jinlong Yan; Jialiang Tang; Bo Zhu (Soil Ecology Letters, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Synthesis, anticancer activity and molecular docking study of triphenylphosphonium-linked derivatives of oleanolic acid - Deshang Li; Bo Wang; Rui Wang; Jianjun Huang; Ruofan Chen; Yi Li; Na Wang; Qianqian Wang; Chenmeng Xu; Wim Dehaen; Qiyong Huai (Natural Product Research, 2026)

A numerical study of damage evolution and crack propagation in backfill bodies of high-temperature thermal energy storage cavities in mines - Rui Zhan; Bo Zhang; Lang Liu; Chao Huan; Huisheng Qu; Huicong Xu; Jin Zhang; Hongjun Xi (Tunnelling and Underground Space Technology, 2026)

Non-progressive orogenesis of the Southern Tibetan Plateau - Xiaoyu Guo; Hengcheng Ying; Lin Chen; Rui Gao; Xiaofan Deng; Zhanwu Lu; Hongda Liang; Bo Xiang; Michael Murphy; Wenhui Li; Xiao Xu (Science Bulletin, 2026)

Integrative analysis of physiology, transcriptomics, and metabolomics unveils mechanisms in soybean (Glycine max (Linn.) Merr) response to alkaline stress - Qian Li; Bo Chen; Ziyu Yang; ChenJing Li; Qing Jing; Qinghong Lu; Rui Ni; Pengzhi Mao; Li Zhang; Xinyong Guo (Plant Science, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Reconstruction of atmospheric CO2 concentration changes during the Aalenian (Middle Jurassic) based on fossil cuticles of Ginkgoites and Czekanowskia from northwestern China - Yu Jiang; Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Bacillus subtilis enhances maize yield by restricting cadmium translocation and modulating ion homeostasis - Haseeb Ahmad; Jiu Yang Mao; Rayyan Khan; Muhammad Ali Shah; Kashif Khan; Muhammad Asad Naseer; Shahid Ali; Rida Rashid; Rui He; Xun Bo Zhou (Journal of Environmental Sciences, 2026)

Mechanism and optimization of NaCl removal from soy sauce residue using low pressure superheated steam drying: Role of condensation and moisture migration - Xin Xu; Jian-Bo Liu; Jia-Cheng Guo; Zhi-Hong Xing; Rui-Fang Wang; Qing Xu (Food Chemistry, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Improved methodology for the qualitative and quantitative analysis of microplastics and nanoplastics in secondary effluent from anaerobic-anoxic-oxic process and advanced MBR technology - Wenjuan Zhang; Rui Miao; Bo Zhang; Miaolu He; Lei Wang; Xudong Wang; Huihui Zhang (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Structural determinants of gelation kinetics in rambutan seed starches: Implications for enhanced precision in 3D food printing - Rui He; Yuxuan Li; Xiaoyu Lin; Bo Xu; Xiang Huo; Weiming Zhang; Tao Yang; Geng Zhong; Fengwei Xie; Ying Chen (Carbohydrate Polymers, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Ultra-highly specific and visual detection of Vibrio pathogens in Porphyra using RPA-coupled CRISPR-LbaCas12a-LFD system - Xu-Xu Luo; Hai-Long Huang; Qi-Qin Liu; Hoi-Yan Kwok; Hai-Tao Ma; Hai-Bo Jiang; Rui Yang (Aquaculture, 2026)

Effects of bacteria-microalgae immobilization on physiology, immunity, microbial composition, and vibriosis resistance of sea cucumber (Apostichopus japonicus) - Xuda Wang; Zunchun Zhou; Ying Dong; Rui Mi; Jingwei Jiang; Danni Liu; Bo Ye; Xiaoyue Wang; Zhenjun Zhao; Boxue Yang; Shilei Li (Aquaculture, 2026)

Determinants of casualty severity in maritime accidents: Evidence from text mining of 581 investigation reports, 2014–2023 - Dongge Liu; Liang Cheng; Bo Ai; Rui Xie; Xidong Wang; Hengshuai Shang (Ocean Engineering, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Numerical simulation of combustion characteristics of kaolin co-firing in a 300 MW fired Zhundong coal boiler - Wangpeng Shi; Jianjiang Wang; Bo Wei; Kunpeng Liu; Shan Wang; Rui Ma; Lijuan Chen; Maierhaba Abudoureheman (Fuel, 2026)

Mechanistic insights into polystyrene micro/nanoplastics-facilitated cadmium trophic transfer and aggravated toxicity along a lettuce-snail terrestrial food chain - Fuyu Guo; Bo Xu; Rui Zhang; Yan Chang; Tingting Chu; Meng Zhu; Fengxiang X. Han; Ruyi Yang (Environmental Pollution, 2026)

Gas bubble dynamics on water electrolysis over Ni/Raney-Ni electrocatalysts - Yafei Qiao; Wei Qin; Haibo Chi; Rui Song; Bo Liu; Can Li (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Exploring Empathic Responses to Others’ Positive and Negative Experiences: Insights from Empathy Subprocesses - Xiao Wu; Xue-Jing Lu; Li-Bo Zhang; Si-Rui Huo; Ya-Zhuo Kong; Li Hu (Neuroscience Bulletin, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Design, synthesis and antitumor activity of triphenylphosphonium-linked derivatives of quinazolinone - Qianqian Wang; Ruofan Chen; Rui Wang; Jianjun Huang; Yinuo Xu; Na Wang; Deshang Li; Chenmeng Xu; Bo Wang; Yi Li; Wim Dehaen; Qiyong Huai (Natural Product Research, 2026)

Ferrate-assisted nonthermal plasma for efficient PFOA degradation in landfill leachate: Mitigating bulk organic interference and enhancing application potential - Changtao Chen; Zhuofan Yu; Rui Zhang; Xuetong Yang; Qintong Wang; Yuxian Ji; Xiaoyu Cheng; Jun Li; Anton Nikiforov; Stijn W.H. Van Hulle; Bo Lai (Water Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Effects of in-situ stress direction and orientation of structure planes on rockburst generation in deep tunnels: 56 case studies - Ben-Guo He; Xiang-Rui Meng; Bo Lin; Hong-Pu Li (Tunnelling and Underground Space Technology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Rubber-based agroforestry systems enhancing soil carbon sequestration through improved soil aggregate stability - Wenxian Xu; Wenjie Liu; Bo Song; Yingying Zhang; Ashar Tahir; Yumiao Cao; Changgeng Kuang; Xinwei Guo; Rui Sun; Xian Zhang; Qiu Yang; Zhixiang Wu (Soil and Tillage Research, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Resistant dextrin/xanthan gum gels protect probiotics for application to ionizing radiation shielding - Minting Wang; Rui Sun; Liuchan Zeng; Shumin Du; Yubao Fang; Bo Zhuang; Bochuan Yuan; Yiguang Jin (Food Research International, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

Exposed and encapsulated NiMo alloy nanoparticles in a N-doped carbon nanotube array for synergistic catalysis toward efficient industrial water splitting - Bo Geng; Rui Chen; Qingyang Song; Gaojie Li (Chemical Engineering Journal, 2026)

Time-series InSAR monitoring and evolution predictive analysis of filling-area subsidence in Yan’an New District - Kangyi Chen; Bo Zhang; Hang Jiang; Jichao Lv; Anmengyun Liu; Yanan Jiang; Rui Zhang (Advances in Space Research, 2026)

Multifunctional deep learning-based mechanical-laser collaborative adaptive precision weeding system for lettuce - Rui Hu; Lei Kong; Wen-Hao Su; Bo-Wen Dong; Yujin Wang; Xiaobin Li; Yankun Peng (Computers and Electronics in Agriculture, 2026)

QuaFT: Quality-guided semantic fault intelligence under corrupted industrial data - Lu Ning; Rui Wang; Xiaoran Wei; Hao Huang; Zonghan Zhang; Zehua Chen; Xiaolu Liu; Bo Zhang; Yao Liu; Hao Gong; Kai Song (Process Safety and Environmental Protection, 2026)

Molecular insight into the structure and formation mechanism of fluid phase in the classical coking theory - Bo Gong; Jie-Ping Wang; Hao-Dong Liu; Rui Guo; Jin-Xiao Dou; Guang-Yue Li; Ying-Hua Liang (Fuel, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

A critical review of inhibitory effects of substrates and organic matter on anammox: mechanisms and mitigation strategies - Rui Zhao; Da Jin; Xiaonong Zhang; Luomiao Ji; Xurui Zhu; Bo Gao; Peng Wu (ENGINEERING Environment, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Finite-time rendezvous of heterogeneous cluster AUVs under intermittent communication and disturbances: A distributed adaptive hybrid observer-controller design - Bo Chen; Zhinan Peng; Rui Luo; Kaibo Shi (Ocean Engineering, 2026)

Unraveling the synergistic impact of calcium ions and pH on the rejection of per- and perfluoroalkyl substances by nanofiltration in complex water matrices - Caihong Liu; Xinyi Cheng; Jingjun Bo; Rui Gao; Ye Shen; Yue Zhi; Dan Song; Qiang He (Journal of Hazardous Materials, 2026)

Carbon emission reduction of bike-sharing around the COVID-19 pandemic based on fine-grained recognition of riding activities - Rui Xin; Mengjie Gong; Jian Yang; Xinping Li; Bo Ai; Ruoxin Zhu (Journal of Cleaner Production, 2026)

Reducing grain arsenic and extracting soil arsenic in paddies by an integrated ridge–furrow and ferrihydrite–PVA membrane system - Jing-Min Yang; Qiao-Rui Ren; Zi-Xin Liu; Xin Wang; Dong-Xing Guan; Ya-Nan Dai; He Pei; Bo Peng; Qin-Bo Qin (Journal of Environmental Sciences, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

The transition from natural to cultivated monoculture grasslands reshapes nematode taxonomic composition without reducing diversity - Rui Yang; Xue Wei; Jinhao Ma; Xiao Ren; Yuying Wang; Bo Zhu; Pengfei Wu (Applied Soil Ecology, 2026)

Changes in litter chemical properties mediate the effects of soil arthropods on the microbial community during litter decomposition in a subalpine forest - Aomiao Wu; Jingru Liu; Rui Yin; Lin Xu; Chengming You; Zhenfeng Xu; Li Zhang; Han Li; Lixia Wang; Sining Liu; Hongwei Xu; Bo Tan (Applied Soil Ecology, 2026)

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Spatio-temporal variations of soil particle size distribution under wind erosion in a temperate grassland: A seven-year landscape scale revisited analysis - Yuxin Feng; Zhuodong Zhang; Zhuoli Zhou; Bo Chen; Ying Li; Xinyu Zou; Rui Xu; Shuran Gao (Soil and Tillage Research, 2025)

Precise construction of Anderson-type polyoxometalate-based covalent organic frameworks for photocatalytic hydrogen peroxide production - Zhang-Di Liu; Zai-Xiang Zhang; Yang Yang; Rui Xing; Zi-Hao Wei; Hou-He Liu; Jiang-Bo Ming; Jin Zhu; De-Yin Wang (Journal of Water Process Engineering, 2025)

A critical review of biochar-enhanced Feammox: Multilevel mechanisms and sustainable applications for nitrogen removal - Luomiao Ji; Xiaonong Zhang; Rui Zhao; Xurui Zhu; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Quantifying nitrogen loss responses to seasonal deluges and droughts: A modeling study in a subtropical agro-forest catchment, upper Yangtze River - Wei Zhang; Xunhua Zheng; Siqi Li; Chunyan Liu; Zhisheng Yao; Shenghui Han; Rui Wang; Kai Wang; Bo Zhu; Minghua Zhou; Xiao Chen; Yong Li (Ecohydrology & Hydrobiology, 2025)

Direct synthesis of highly efficient NIR-I emitting core-only InP quantum dots via multi-ligand synergy - Rui Jiang; Jie Zhao; Yifei Qiao; Bo Tan; Jialin Yin; Zhenyu Dai; Shiliang Mei; Wanlu Zhang; Ruiqian Guo (Chemical Engineering Journal, 2025)

Functional insights into JrWOX5: a WOX transcription factor regulating adventitious rooting and plant architecture in walnut - Rui-xue Gao; Pu Zhang; Ying-ying Chang; Li Song; Xiao-bo Song; Dong Pei (Plant Cell Reports, 2025)

Time trend of urine metal levels in preschool children in the electronic waste recycling area and its association with hemoglobin levels - Rongyi Kang; Jieting Chen; Kaihui Li; Rui Sun; Jian Zhang; Chenxu Dai; Xijin Xu; Bo Xie; William W. Au; Lei Tan; Xia Huo (International Archives of Occupational and Environmental Health, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Typology-driven framework for revitalizing urban leftover spaces: Systematic review of practices and future research directions - Rui Qiao; Yi Sun; Siqiang Wang; Bo Lan; Chun Yin Chung (Land Use Policy, 2025)

Simple and economical photoelectrode modification for efficient ranitidine removal: Improved surface reactivity and switchable radical/non-radical pathways - Jiajun An; Yanan Li; Lei Wang; Jiajin Hao; Lujie Nie; Bo Gao; Xudong Wang; Jin Wang; Rui Miao; Miaolu He; Danxi Huang (Journal of Hazardous Materials, 2025)

The correlation between temperature change and lung cancer risk altered by air particulate pollutants: Nationwide analysis - Shenxuan Zhou; Yanchi Wang; Zhenyu Li; Yiran Liu; Rui Zhu; Bo Liu; Jiacan Yuan; Mingna Wu; Jing Xiao; Hanpeng Lai; Anhui Ning; Yan Zhang; et al. (Journal of Cleaner Production, 2025)

A multiscale peridynamic simulation on thermal-mechanical coupling behavior and damage failure mechanism of granite - Heng Li; Sheng-Qi Yang; Rui Yong; Shi-Gui Du; Bo-Wen Sun; Su-Sheng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Molecular insights into the adsorption behavior of PFAS on montmorillonite, polyethylene, and polypropylene: A molecular dynamics study - Qiao Wang; Rui Xu; Fusheng Zha; Long Xu; Bo Kang; Heming Han (Computers and Geotechnics, 2025)

Creep deformation characteristics and microscopic mechanism of undisturbed soils of the landslide sliding zone in the Jinpingzi area - Ruihong Wang; Rui Zhao; Ge Zhang; Bo Lu (Bulletin of Engineering Geology and the Environment, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Mechanisms of cypermethrin degradation and remediation by Rhodococcus sp. H-3: Insights from comparative genomics, hydrolase CymE1 secretory expression, and bacterial community analysis - Guoqiang Zhao; Wenjing Chen; Rongrong Zhang; Rui Zhang; Bo Jiang; Ruyan Hou; Xing Huang (Journal of Hazardous Materials, 2025)

Tfh cell-mediated impairment of rotavirus-specific antibodies by PAH and PFAS co-exposure in seropositive children - Jian Zhang; Jieting Chen; Rongyi Kang; Chenxu Dai; Bo Xie; Kaihui Li; Rui Sun; Xiangbin Zheng; Lei Tan; Xijin Xu; Xia Huo (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Decoding the spatiotemporal dynamics of cropland carbon emission drivers in China: A machine learning-based analysis - Hanbing Li; Xiaobin Jin; Rongqin Zhao; Bo Han; Xinyuan Liang; Rui Sun (Journal of Cleaner Production, 2025)

Advances in the application of carbon materials for anammox enhancement: A comprehensive review - Bo Gao; Xiaonong Zhang; Rui Zhao; Xurui Zhu; Luomiao Ji; Peng Wu (Journal of Environmental Management, 2025)

The organic matrix: An in-depth review of kerogen and its significance - Kouqi Liu; Hongyan Qi; Zhizhong Wang; Bo Liu; Yamin Wang; Zhengchen Zhang; Hong Zhang; Rui Yang; Liangliang Jiang; Mehdi Ostadhassan (Fuel, 2025)

Utilizing a three-zone control model of adaptive concentrating photovoltaic facade to enhance visual comfort and energy benefits - Bo Wang; Yifan Xu; Hao Wang; Xinshuo Zhang; Yuan Chen; Rui Tang; Ayin Yan; Mengli Zhang; Ying He (Energy and Buildings, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Recent advances in nanomaterial biosensors for the detection of antibiotics to ensure food safety - Bo Long; Qian Zhang; Lintong Zhang; Qiongqiong Xing; Qi Liu; Liying Deng; Fangfang Qu; Rui You; Xuan Wei; Dapeng Ye; Zhanhui Yuan (Chemical Engineering Journal, 2025)

CuCo nanoparticles encapsulated with nitrogen-doped carbon nanotubes for efficient and stable alkaline saline water splitting - Bo Geng; Rui Chen; Gaojie Li; Kaikai Liu; Yujin Chen (Chemical Engineering Journal, 2025)

Evolution of surface ozone pollution in Yangtze Rriver Delta between 2019 and 2022: influences of meteorology and emissions - Ying Zhang; Fenfen Zhang; Mei Wan; Yu Bo; Kebin He; Rui Liu (Atmospheric Environment, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Water resource assessment in data-scarce hydrological regions based on limited underwater survey points - Chen Wang; Bo Zhang; Rui Zhu; Ruonan Wei; Zhen Bian (Environmental Monitoring and Assessment, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Modification of red mud using K/Ca doping to enhance its oxygen-donating performance in chemical looping gasification of biomass waste - Rumeng Zhang; Xiao Li; Rui Dong; Xianliang Meng; Bo Zhang; Shi Yu (Biomass and Bioenergy, 2025)

MLWNNR: LncRNA-Disease Association Prediction with Multi-Kernel Learning-Driven Weighted Nuclear Norm Regularization - Guo-Bo Xie; Hao-Jie Xu; Guo-Sheng Gu; Zhi-Yi Lin; Jun-Rui Yu; Rui-Bin Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Influence of biomass ashes on the structural evolution and oxygen-donating capacity of red mud during chemical looping gasification - Xiao Li; Rumeng Zhang; Rui Dong; Xianliang Meng; Pei Li; Chao Ni; Bo Zhang (Waste Management, 2025)

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Optimization of discharge parameters for high-voltage pulse crushing technology − A review - Bo Zhang; Rui Han; Peng Gao; Shuai Yuan; Yanjun Li; Honghao Zhang (Minerals Engineering, 2025)

Insights into ROL-driven and ROS-mediated metalloid oxidation and sequestration in the soil-rice iron barrier system - Jing-Min Yang; Xin Wang; Dong-Xing Guan; Rui Huang; Xiong-Hui Ji; Yun-He Xie; Bo Peng; Qin-Bo Qin (Journal of Hazardous Materials, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Insights from dynamics, mechanisms, factors and mitigation strategies of salt precipitation for CO2 geo-storage within saline aquifer - Bo Wang; Yuanhao Chang; Rui Ma; Xiangzeng Wang; Hongyang Wang; Fanhua Zeng (Earth-Science Reviews, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

The combined application of cis-cyclo(L-Phe-L-Pro) with antimicrobial proline-based 2,5-diketopiperazines significantly enhances anti-breast cancer activity by selectively targeting cancer stem cells - Rui Liu; Bo Sun; Sa-Ouk Kang; Yeonju Hong; Ji-Yoon Yeo; Jun-Hua Wang; Min-Kyu Kwak (Chemico-Biological Interactions, 2025)

Impact of Clay Minerals on the Characteristic Strength and Nonlinear Dissipative Energy Modeling of Water-Saturation Mudstone - Yugang Cheng; Rui Wu; Bo Hu; Mengru Zeng; Yong Zhao; Gexin Wan; Xuefu Zhang; Jinjie Yang (Rock Mechanics and Rock Engineering, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Glacial debris flow hazard assessment and multi-parameter probabilistic model: a case study of Guxiang Gully - Lili Chang; Taixia Wu; Haixia He; Bo Li; Rui Zhang (Landslides, 2025)

Modulating expression of Frankliniella occidentalis glutathione S-transferase genes to adapt to host shifts - Tao Zhang; Li Liu; Ding-Yin Li; Wen-Bo Yue; Guang Zeng; Dan Zhou; Jun-Rui Zhi (Arthropod-Plant Interactions, 2025)

Drivers of ecosystem service trade-off changes in different climate zones: a case study of the Sichuan–Yunnan–Loess plateau ecological shelter, China - Hao-Rui Li; Shuai Ma; Ming Zhang; Yun-Ke Yin; Hai-Bo Hu; Liang-Jie Wang; Jiang Jiang (Environment, Development and Sustainability, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Improving agricultural mulching to reduce environmental footprint and enhance economic profit across China - Huihui Wei; Yifan Yang; Li Zhang; Zutao Ouyang; Matthew Tom Harrison; Ke Liu; Guojun Sun; Gary Y. Gan; Feng-Min Li; Li Dong; Rui Wang; Bo Wang; et al. (Resources, Conservation and Recycling, 2025)

Controllable synthesis of bimetallic Cu-Zn conjugated polymer microflowers with splendid laccase- and antioxidase-like activities for colorimetric detection of organic pollutants and eliminating cigarette smoke radicals - Shu-Chang Zhao; Dan Wu; Ya-Nan Kong; Jing-Jing Luo; Bo-Yi Yuan; Rui-Lin Liu (Journal of Hazardous Materials, 2025)

A new three-dimensional peak shear strength criterion of rock joints considering true-sheared asperities - Yingchun Li; Yue Cui; Yuzong Li; Rui Yong; Bo Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Study on the dynamic characteristics of hybrid ceramic ball bearings in a horizontal canned motor reactor coolant pump - Xiaohang Chen; Danrong Song; Jinqi Lu; Bo Wei; Rui Xu; Dezhong Wang (Annals of Nuclear Energy, 2025)

Biochar mitigates greenhouse gas emissions from bulk soil in wheat-corn rotation system by inhibiting biochemical decomposition - Debo He; Rui Yang; Yan Fu; Dongni Hu; Han Ma; Xiaoguo Wang; Zhixin Dong; Bo Zhu (Agriculture, Ecosystems & Environment, 2025)

Unlocking the future potential of SWATH-MS: Advancing non-target screening workflow for the qualitative and quantitative analysis of emerging contaminants - Di Xia; Guofang Pan; Yaxiong Liu; He Liu; Bo Zhao; Jiahui Wu; Ting Tang; Guining Lu; Rui Wang (Water Research, 2025)

Bisphenol S promotes clear cell renal cell carcinoma progression by modulating the WNT5A-dependent EMT pathway - Hua Zhang; Fei Lin; Bo-Han Lin; Xiong-Lin Sun; Qing-Shui Zheng; Rui Gao; Yong Wei; Shao-Hao Chen; Xue-Yi Xue (Toxicology, 2025)

Testing micro-aliquot SGC and LnTn methods for age determination up to 780 ka using coarse K-feldspar grains from Nihewan Basin, northern China - Shengxia Xu; Xue Rui; Yujie Guo; Bo Li (Quaternary Geochronology, 2025)

Mechanism of quartz flotation separation from gypsum using tetradecyl trimethyl ammonium chloride: Guiding the improvement of phosphogypsum quality - Haodong Shi; Liuyi Ren; Shenxu Bao; Yimin Zhang; Anh V. Nguyen; Bo Chen; Weifeng Li; Rui Huang; Yanqi Zeng; Sidi Lou (Minerals Engineering, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Superior properties of biochar contribute to soil carbon sequestration and climate change mitigation - Debo He; Rui Yang; Yan Fu; Bo Zhu (Journal of Environmental Chemical Engineering, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Injectable dual-network hydrogel for phototherapy and immunomodulation in the treatment of MRSA-infected and diabetic wound - Shengfei Bao; Aodi Jiang; Li Peng; Fuying Liao; Ga Liu; Li Chen; Peng Zhou; Zhen Zhu; Rui L. Reis; Subhas C. Kundu; Lian Duan; Bo Xiao; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Label-free urinary protein detection through machine learning analysis of single droplet evaporation patterns - Ruyue Yang; Nannan Cao; Yan Yang; Shujuan Guan; Chao Yang; Bo Situ; Yongyu Rui; Hongwei Zhou; Lei Zheng (Analytica Chimica Acta, 2025)

Effect of oligosaccharides from Enteromorpha clathrata on tolerance of wheat (Triticum aestivum L.) seedings to saline-alkali stress - Yinglu Wu; Chunying Du; Rui Xiao; Bo Zhu; Xiuchao Song; Xinyu Wang; Yimin Qin; Peng Wang (Algal Research, 2025)

Rodent-induced grassland degradation increases annual non-CO2 greenhouse gas fluxes and NO losses despite CH4 uptake enhancement - Zhisheng Yao; Rui Wang; Han Zhang; Lei Ma; Xunhua Zheng; Chunyan Liu; Wei Zhang; Yanqiang Wang; Bo Zhu; Klaus Butterbach-Bahl (Agricultural and Forest Meteorology, 2025)

Systemic resistance of kidney bean plants induced by exogenous CaCl2 and western flower thrips infestation - Guang Zeng; Jun-Rui Zhi; Tao Zhang; Wen-Bo Yue; Ding-Yin Li; Mao Ye (Arthropod-Plant Interactions, 2025)

White matter microstructural and cognitive function changes in bipolar depression patients with suicidal ideation - Junfan Liang; Rui Fan; Xinyin Guo; Hua Liu; Xuehua Li; Jixiang Yuan; Kezhi Liu; Xuemei Liang; Bo Xiang (Brain Imaging and Behavior, 2025)

A novel large linear stroke high-static-low-dynamic stiffness vibration isolator with high magnetic negative stiffness and compactness - Wuhui Pan; Hongyu Xie; Pengfei Ai; Rui Liu; Bo Gao; Shilin Xie; Yajun Luo; Yahong Zhang (Engineering Structures, 2025)

Permafrost thawing characterization in engineering scale by multi-geophysical methods: A case study from the Tibet Plateau - Junkai Ge; Huaifeng Sun; Rui Liu; Zhiyou Huang; Bo Tian; Lanbo Liu; Ziqiang Zheng (Engineering Geology, 2025)

Radiochromic perovskite La2MgZrO6:Pr for X-ray imaging and ionizing radiation detection - Zi-Hao Chen; Qiang Tang; Jian-An Zeng; Haijiao Xie; Rui Zou; Jing Wang; Bo-Mei Liu (Chemical Engineering Journal, 2025)

ZnCo2O4/LaAlO3 transparent pn junction towards enhanced photoelectric response and stability via interfacial homogeneous high entropy oxide perovskite La(Cu0.2Co0.2Ni0.2Fe0.2Mn0.2)O3 QDs - Bo He; Yujia Huang; Rui Wang; Dingwei Wang; Chengyu Jia; Jun Cao; Lei Shi; Jiaqi Pan; Zhiguo Zhao; Chaorong Li (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Energy Release Efficiency and Mechanisms of Mining-Induced High-Energy Earthquakes in China - Zi-Bo Wang; Rui-Feng Liu; Ting-Ting Wang; Yi-Xiao Zhang; Xiao Ren (Rock Mechanics and Rock Engineering, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

Histone H3K36 methyltransferases NSD1 and SETD2 are required for brain development - Bo Chen; Chenyang Zhang; Huanwen Rui; Dan Shen; Zhuxi Huang; Weijun Feng (Human Genetics, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Remarks on strong phase shifts in weak nonleptonic baryon decays - Hong-Jian Wang; Pei-Rong Li; Xiao-Rui Lyu; Jusak Tandean; Hai-Bo Li (Science Bulletin, 2025)

Evaluation of a lightweight water circulation cooling blanket for the prevention of exertional heat stroke - Xin Li; Xin Wang; Rui Yan; Qing Song; Bo Ning; Shuyuan Liu; Qian Wang (Journal of Thermal Biology, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

A magnetic nanoreactor with microenvironment regulation capability for targeted and enhanced tumor chemodynamic therapy - Xia-Nan Li; Qin-Ying Tang; Meng-Cheng Tang; Hai-Rui Deng; Kang Hu; Ling-Feng Pan; Shi-Bo Wang; Bin Li; Xiang-Dong Kong (Chemical Engineering Journal, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Suitability and Bearing Behavior of PHC Pipe Piles in Underlying Mudstone - Qing-rui Feng; Hao-feng Xing; Hong-bo Chen; Hua Wei (Geotechnical and Geological Engineering, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Ratio Fluorescence Sensor Based on Bimetal MOFs for the Detection of Hg2+and H2O2 - Bo-Ming Han; Hao-Rui Zhang; Wen-Jie Gao; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Fluorescence, 2025)

Monitoring dust retention variations in different functional zones based on leaf magnetism and the influence of green belt spatial layouts on leaf dust retention - Ziwei Tao; Shuxuan Li; Bo Wang; Yi Xie; Rui Wang; Linglin Hu; Jia Jia; Junhui Zhang (Environmental Monitoring and Assessment, 2025)

Numerical and experimental studies on the hydrodynamic performance of a composite cylindrical perforated-wall caisson breakwater - Zi-bo Xia; Xin-yu Wang; Xiao Liu; Rui-jia Jin; Bao-lei Geng; Yong Liu (Ocean Engineering, 2025)

Geochemical constraints on subduction-related mantle metasomatism of the Tiébaghi ophiolitic lherzolite in New Caledonia - Pengjie Cai; Dongyang Lian; Jonathan C. Aitchison; Dominique Cluzel; Renjie Zhou; Huichao Rui; Rongzong Bo; Haitao Ma; Jingsui Yang; Ahmed E. Masoud (Lithos, 2025)

Microstructural regulation of Ir(III) complexes for enhanced photocytotoxicity in photodynamic cancer therapy - Xiaomeng Liu; Qing Zhang; Jiaqi Li; Zhewen Deng; Senqiang Zhu; Bo Ma; Rui Liu; Hongjun Zhu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Zearalenone delays tissue regeneration by dysregulating neutrophil balance in zebrafish (Danio rerio) larvae - Rui Luo; Bo Wang; Rui Luo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Dual-targeting of PDPN-expressing synovial fibroblasts and macrophages via CLEC-2-engineered exosomes for osteoarthritis therapy - Bo Yu; Rui Peng; Zitao Liu; Shanchuang Chen; Nanjun Xu; Qingjun Yang; Zhengang Zha; Bolai Chen; Tao Jiang; Tao Gui; Songwei Huan (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Subsurface drip irrigation with micro-nano bubble hydrogen water improves the salt tolerance of lettuce by regulating the antioxidant system and soil bacterial community - Jian Wang; Xin Guo; Qihang Zhao; Rui Chen; Guanlin Li; Bo Zhou; Pengfei Cheng (Applied Soil Ecology, 2025)

Scale-shift governor with analytical solutions for spacecraft formation collision avoidance - Bo Meng; Leyu Chen; Haichao Gui; Rui Zhong (Advances in Space Research, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Monitoring nutrient and beneficial elements in the topsoil: the function of weathered background and later surficial process on their distribution - Bo Zhang; Kai-Ning Lv; Huan Li; Qin-Rui Zhang; Zhi-Qiang Yin; Wei-Zhi Zhou; Guo-Li Yuan (Environmental Monitoring and Assessment, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Revealing the relationship between 2D/3D built environment and jobs-housing separation coupling nonlinearity and spatial nonstationarity - Rui An; Zhaomin Tong; Bo Tan; Qiangqiang Xiong; Yuanyuan Luo; Yaolin Liu; Linchuan Yang; Xiping Yang (Journal of Transport Geography, 2025)

Anammox sludge granulation and synergy with comammox: A critical review - Rui Zhao; Xiaonong Zhang; Da Jin; Xurui Zhu; Luomiao Ji; Bo Gao; Peng Wu (Journal of Environmental Chemical Engineering, 2025)

Gradient ethanol extracts of Coreopsis tinctoria buds: Chemical and in vitro fermentation characteristics - Shang Gao; Tiantian Li; Zhao-Rong Li; Bingwu Liao; Mouming Zhao; Chunxia Zhou; Donghui Luo; Rui-Bo Jia (Food Chemistry, 2025)

A review of emission characteristics and risk assessments of volatile organic compounds in petrochemical industry areas - Jinchan Peng; Yunxia Feng; Anshan Xiao; Bo Li; Dewu Ding; Guolong Wang; Rui Dong (Environmental Pollution, 2025)

Shear wave velocity prediction based on bayesian-optimized multi-head attention mechanism and CNN-BiLSTM - Wenzhi Lan; Yunhe Tao; Bin Liang; Rui Zhu; Yazhai Wei; Bo Shen (Computers & Geosciences, 2025)

An effective method for distinguishing extracellular and intracellular nanoparticles through chemical extractions - Bin Huang; Jie-Yu Chang; Bo-Wen Li; Lu He; Rui-Si Liang; Huan He; Ai-Jun Miao; Hui Li (Aquatic Toxicology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

An efficient, high-throughput enrichment system for the rapid detection of E. coli at low concentrations in water - Binghuan He; Fangzhou Zhang; Pengfei Gong; Rui Sun; Jianxin Cheng; Chenghui Jin; Bo Liu; Jianlong Zhao; Shilun Feng; Bei Li (Analytica Chimica Acta, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Bioenhanced remediation of dibutyl phthalate contaminated black soil by immobilized biochar microbiota - Yue Tao; Yao Wang; Yunhe Cui; Rui Sun; Bo Zhang; Jianhua Qu; Hongguang Cai; Ying Zhang (Journal of Environmental Management, 2025)

Defect-induced precise synthesis of ultrasmall Ir1Sn1 intermetallic nanoparticles for enhanced propane dehydrogenation - Mingshan Wang; Rui Ma; Jiahao Zhang; Junbo Wang; Zhilin Wu; Guojun Zou; Bo Zhou (Fuel, 2025)

Extraction of phenolic acids and tetramethylpyrazine in Shanxi aged vinegar base on vortex-assisted liquid-liquid microextraction-hydrophobic deep eutectic solvent: COSMO-RS calculations and ANN-GA optimization - Baoqing Bai; Siyuan Meng; Yanli Guo; Ziqing Zhang; Rui Chen; Tao Bo; Jinhua Zhang; Sanhong Fan; Yukun Yang (Food Chemistry, 2025)

Study on the heat transfer characteristics of cemented backfill heat exchangers with a horizontally penetrating rough fracture under groundwater advection - Rui Zhan; Bo Zhang; Lang Liu; Chao Huan; Yujiao Zhao; Xiaoyan Zhang; Xueli Wang (Computers and Geotechnics, 2025)

Enhanced wastewater treatment using biochar-supported layered-double-hydroxide composites - Ao Huang; Nan Zhang; Qian-Bin Wang; Bo-Han Zhao; Rui-Bao Zhang; Ming Cheng; Chen Shi; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Study on the high-temperature corrosion mechanism of boiler steel 15CrMoG in ammonia-coal co-firing environment - Tiantian An; Bo Wei; Rui Ma; Lijuan Chen; Shan Wang; Meng Xu; Kunpeng Liu (Fuel, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Chocolate pattern-inspired flexible thick electrodes: A facile mechanical imprinting method - Huadong Gao; Yang Xiong; Bo Rui; Yinhua Bao; Yicheng Song; Bo Lu; Junqian Zhang (Chemical Engineering Journal, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Novel insights into Feammox coupled with the NDFO: A critical review - Luomiao Ji; Xiaonong Zhang; Xurui Zhu; Bo Gao; Rui Zhao; Peng Wu (Science of The Total Environment, 2024)

A critical review of Mnammox coupled with the NDMO for innovative nitrogen removal - Xurui Zhu; Xiaonong Zhang; Bo Gao; Luomiao Ji; Rui Zhao; Peng Wu (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

Room temperature shape self-adjustable tough hydrogel based on multi-physical crosslinking - Jun-Bo Hou; Zhi-Chao Jiang; Yao-Yu Xiao; Rui-Dong Cheng; Yue Zhao (Chemical Engineering Journal, 2024)

Direct near-infrared laser ignition of CL-20 by introducing DATNBI as a bi-functional additive: Energetic photosensitizer and self-assembly stimulator - Ping Ye; Heng Ding; Bo Yang; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

A critical review of impact and synergistic mechanisms of iron and co-elements in anammox - Bo Gao; Xiaonong Zhang; Xurui Zhu; Luomiao Ji; Rui Zhao; Peng Wu (Chemical Engineering Journal, 2024)

Cu2WS4 with high-exposure {0 0 1} surfaces promotes efficient charge separation in ZnIn2S4 - Rui Li; Shuangjun Li; Luyang Zuo; Xiangping Xiao; Huitao Fan; Bo Li; Liya Wang (Chemical Engineering Journal, 2024)

Forest fragmentation effects on plant-animal interaction do not always show consistent patterns – Evidence from a seed removal experiment of 31 woody species - La-Mei Wu; Rui-Chang Quan; Bo Wang (Biological Conservation, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Study on the source identification and migration and transformation characteristics of heavy metal pollution in sediments of Chaohu Lake Tongyang River Basin - Zhenyu He; Yanjun Li; Bo Kang; Rui Li; Kun Chen; Jie Yang; Yuezan Tao (Environmental Monitoring and Assessment, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Weights embedding Informer prediction algorithm-based fault diagnosis framework for nuclear power plant - Tan Canyi; Zheng Wei; Wang Bo; Tan Sichao; Liang Biao; Li Jiangkuan; Han Rui; Ke Zhiwu; Tian Ruifeng (Annals of Nuclear Energy, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

A critical review of comammox and synergistic nitrogen removal coupling anammox: Mechanisms and regulatory strategies - Da Jin; Xiaonong Zhang; Xingxing Zhang; Li Zhou; Zixuan Zhu; Ufoymungu Kisa Deogratias; Zhiqiang Wu; Kangyu Zhang; Xu Ji; Ting Ju; Xurui Zhu; Bo Gao; et al. (Science of The Total Environment, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Screening structure and predicting toxicity of pesticide adjuvants using molecular dynamics simulation and machine learning for minimizing environmental impacts - Zhenping Bao; Rui Liu; Yanling Wu; Songhao Zhang; Xuejun Zhang; Bo Zhou; Paul Luckham; Yuxia Gao; Chenhui Zhang; Fengpei Du (Science of The Total Environment, 2024)

Farmland’s silent threat: Comprehensive multimedia assessment of micropollutants through non-targeted screening and targeted analysis in agricultural systems - Yang Qiu; Lijun Liu; Caifei Xu; Bo Zhao; Hang Lin; He Liu; Weixuan Xian; Han Yang; Rui Wang; Xingjian Yang (Journal of Hazardous Materials, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Efficient elimination of antibiotic resistome in livestock manure by semi-permeable membrane covered hyperthermophilic composting - Bo Sun; Zhihui Bai; Rui Li; Manjiao Song; Jian Zhang; Jiancheng Wang; Xuliang Zhuang (Bioresource Technology, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Graph deep learning recognition of port ship behavior patterns from a network approach - Rui Xin; Jiale Pan; Fanlin Yang; Xiongfeng Yan; Bo Ai; Qianran Zhang (Ocean Engineering, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Study on optimized culture of microbial strains and their ability in wax removal and viscosity reduction of paraffin-based crude oil - Bo Wang; Yuanhao Chang; Rui Ma; Qiushi Zhang; Weiqiang Wang (Fuel, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Research Overview on Sugarcane Deep Processing and Comprehensive Utilization in China - Gan-Lin Chen; Jing Chen; Bo Lin; Ling-Zhi Zhao; Feng-Jin Zheng; Krishan K. Verma; Yang-Rui Li (Sugar Tech, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A review of distribution and functions of extracellular DNA in the environment and wastewater treatment systems - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Bo Zhang (Chemosphere, 2024)

The interaction of endorepellin and neurexin triggers neuroepithelial autophagy and maintains neural tube development - Lei Lu; Meizhu Bai; Yufang Zheng; Xiukun Wang; Zhongzhong Chen; Rui Peng; Richard H. Finnell; Tongjin Zhao; Chengtao Li; Bo Wu; Yunping Lei; Jinsong Li; et al. (Science Bulletin, 2024)

Study on the influence of a single fracture on the performance of backfill heat exchangers in underground stopes - Bo Zhang; Wenxuan Zhang; Rui Zhan; Lang Liu; Chao Huan; Yujiao Zhao; Xiaoyan Zhang (Geothermics, 2024)

Separation, enrichment and cytoprotection of antioxidant peptides from Xuanwei ham using aqueous two-phase extraction - Rui-hong Xie; Shan Xiao; Xuan Chen; Bo Wang; Yao-yao Hu; Ji-hui Wang (Food Chemistry, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

The identification of toll-like receptor genes in large yellow croaker (Larimichthys crocea): provides insights into its environmental adaptation to biological and abiotic stresses - Ting-Yan Yao; Qing-Tao Miao; Xuan-Yang Sun; Chen Rui; Qing-Ping Xie; Xu-Bo Wang (Frontiers in Marine Science, 2024)
Large yellow croaker ( Larimichthys crocea ), the most developing fish of China, suffering from both biotic and abiotic stressors. A genome-wide study was performed for the first time to investigate the roles of Toll-like receptor genes in large yellow croaker ( LcTLRs ) working in hypoxia response and Aeromonas hydrophila infection. 12 TLR genes were identified and annotated, and phylogenetic tree, analysis of structure and motifs demonstrated that TLRs were highly conserved. To further investigate the LcTLRs under environmental stress, expression pattern analysis of hypoxic response and Aeromonas hydrophila infection revealed that there were nine and six members of LcTLRs showing significant differential expression, indicating that they were concerned in hypoxia stress and disease responses. Meanwhile, their expression levels were validated utilizing qPCR. Taken together, a greater appreciation and understanding of TLRs function in the reaction to biotic and abiotic stress would ultimately lead to more efficiently environmental adaptation in large yellow croaker.

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Reduction of heavy metals in municipal solid waste incineration fly ash followed by making transparent glass - Hanlin Shen; Bingjie Lou; Bo Liu; Junjie Zhang; Xiaoyan Zhang; Jun Liu; Rui Zhang; Mingcui Chen; Shengen Zhang (Waste Management, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Photoactive cationic conjugated microporous polymers containing pyrimidine with an ‘adsorption-kill’ antibacterial strategy for infected wound healing - Ga Liu; Shengfei Bao; Jiahao Shi; Chunyu Xie; Fuying Liao; Lingshuang Wang; Fan Zheng; Rui L. Reis; Subhas C. Kundu; Bo Xiao; Xiao Yang; Lian Duan (Chemical Engineering Journal, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

3D gravity inversion using cycle-consistent generative adversarial network - Shu-Bo Qiao; Hou-Pu Li; Rui Qi; Yu-Jie Zhang; Shi-Min Xie (Applied Geophysics, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Hydrothermal carbonization of Chinese medicine residues: Formation of humic acids and combustion performance of extracted hydrochar - Rui Wang; Xiaoyuan Zheng; Zhenyang Feng; Yuheng Feng; Zhi Ying; Bo Wang; Binlin Dou (Science of The Total Environment, 2024)

Performance enhancement, bacterial communities optimization and emerging pollutants elimination by microalgal-bacterial consortium for treating aquaculture pond sediments - Xuda Wang; Shilei Li; Rui Mi; Ying Dong; Jingwei Jiang; Xiaoyan Guan; Xiaoyue Wang; Bo Ye; Danni Liu; Zhenjun Zhao; Xuewen Gao; Zunchun Zhou (Journal of Environmental Management, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Insights into “wheat aroma”: Analysis of volatile components in wheat grains cultivated in saline–alkali soil - Qianqian Sun; Rui Zhang; Yu Liu; Liya Niu; Hongyan Liu; Peifang Ren; Bianna Xu; Boli Guo; Bo Zhang (Food Research International, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Assessment and management for future habitat risks under the implementation of China's territorial spatial planning: A case study from Hainan Island - Xiaolin Zhang; Xiaobin Jin; Xinyuan Liang; Xu Shi; Rui Sun; Wenjie Zhu; Jinhuang Lin; Bo Han; Yinkang Zhou (Environmental Impact Assessment Review, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Pseudomonas aeruginosa regulator PvrA binds simultaneously to multiple pseudo-palindromic sites for efficient transcription activation - Yibo Zhu; Bingnan Luo; Xingyu Mou; Yingjie Song; Yonghong Zhou; Yongbo Luo; Bo Sun; Youfu Luo; Hong Tang; Zhaoming Su; Rui Bao (Science China Life Sciences, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Two microbes assisting Miscanthus floridulus in remediating multi-metal(loid)s-contaminated soil - Yunhua Xiao; Jingjing Ma; Rui Chen; Sha Xiang; Bo Yang; Liang Chen; Jun Fang; Shuming Liu (Environmental Science and Pollution Research, 2024)

Vanadium isotope evidence for seawater contribution to V enrichment/mineralization in early Cambrian metalliferous black shales - Lin-Hui Dong; Wei Wei; Lingang Xu; Yi-Bo Lin; Ze-Rui Liu; Songqi Pan; Zhenhua Jing; Fang Huang (Science Bulletin, 2024)

Sesquiterpenes from Inula macrophylla and their anti-neuroinflammatory activity - Rui Ma; Bakhrom Komilov; Cheng-Bo Wang; Komila Alibekovna Eshbakova; Jun-Li Yang; Wei Ha; Yan-Ping Shi (Phytochemistry Letters, 2024)

Geothermal fluid chemistry and isotope for interpreting the formation of complex geothermal system in the Gonghe Basin, northeastern Tibetan Plateau - Rui Lu; Wenping Xie; Bo Liu; Shengsheng Zhang; Jinshou Zhu; Wenjing Lin (Journal of Hydrology, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Enhancing compound confidence in suspect and non-target screening through machine learning-based retention time prediction - Dehao Song; Ting Tang; Rui Wang; He Liu; Danping Xie; Bo Zhao; Zhi Dang; Guining Lu (Environmental Pollution, 2024)

Effects of belt trusses on drift control of frame-core tube structures - Wen-Bo Wang; Hong-Song Hu; Rui-Tao Wang; Yi-Chao Gao; Zi-Xiong Guo (Engineering Structures, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Long-term straw return to a wheat-maize system results in topsoil organic C saturation and increased yields while no stimulating or reducing yield-scaled N2O and NO emissions - Zhisheng Yao; Yanqiang Wang; Rui Wang; Xiaogang Wang; Yan Wang; Xunhua Zheng; Chunyan Liu; Bo Zhu; Minghua Zhou; Yan Liu; Klaus Butterbach-Bahl (Agricultural and Forest Meteorology, 2024)

Investigating the spatio–temporal characteristics of lower atmospheric ducts across the China seas by performing a long–term simulation using the WRF model - Qi Liu; Xiaofeng Zhao; Jing Zou; Tong Hu; Zhijin Qiu; Bo Wang; Zhiqian Li; Chaoran Cui; Rui Cao (Frontiers in Marine Science, 2024)
In this work, a diagnostic scheme for lower atmospheric ducts was established based on the Weather Research and Forecasting (WRF) model. More specifically, a 10-year simulation test was conducted for the China seas to investigate the spatio-temporal characteristics of the lower atmospheric ducts phenomenon. Compared with the sounding data, the long-term simulations showed a high temporal correlation and the root mean square error of the modified atmospheric refractivity remained between 4 M and 7 M. Based on the simulations, significant regional differences in the occurrence probability of lower atmospheric ducts were detected from south to north. Among them, the surface ducts near the sea surface exhibited the highest occurrence probability, with higher probabilities being recorded in autumn and winter, and the probability gradually increased with the decreasing latitude. The spatio-temporal characteristics of duct height, thickness, and strength were generally consistent. In the seas at mid-latitudes, strong ducts mostly occurred in the spring and autumn, with the single-layer ducts being predominant and the first layer duct showing stronger characteristics than the second layer. In the lower latitude regions, the situation was exactly the opposite. The first duct layer, which existed throughout the year, exhibited weaker characteristics with less pronounced seasonal variations. On the other hand, the second duct layer demonstrated stronger features.

Recent advances in the role of dissolved organic matter during antibiotics photodegradation in the aquatic environment - Yinghui Guo; Bo Peng; Jinggan Liao; Weicheng Cao; Yaojun Liu; Xiaodong Nie; Zhongwu Li; Rui Ouyang (Science of The Total Environment, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Amylose content controls the V-type structural formation and in vitro digestibility of maize starch-resveratrol complexes and their effect on human gut microbiota - Deyi Yang; Qiyong Guo; Rui Li; Ling Chen; Bo Zheng (Carbohydrate Polymers, 2024)

Let-7b-TLR7 Signaling Axis Contributes to the Anesthesia/Surgery-Induced Cognitive Impairment - Liyun Deng; Rui Gao; Hai Chen; Bo Jiao; Changteng Zhang; Liuxing Wei; Caiyi Yan; Shixin Ye-Lehmann; Tao Zhu; Chan Chen (Molecular Neurobiology, 2024)

Reproducibility in nontarget screening (NTS) of environmental emerging contaminants: Assessing different HLB SPE cartridges and instruments - Wenhao Jia; He Liu; Yini Ma; Guolong Huang; Yaxiong Liu; Bo Zhao; Danping Xie; Kaibo Huang; Rui Wang (Science of The Total Environment, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Heat stress enhances the occurrence of erythromycin resistance of Enterococcus isolates in mice feces - Lingxian Yi; Rui Xu; Xiaowu Yuan; Zining Ren; Huihui Song; Huamin Lai; Zhihua Sun; Hui Deng; Bo Yang; Daojin Yu (Journal of Thermal Biology, 2024)

Nickel isotope fractionation during intense weathering of basalt: Implications for Ni output from continental weathering - Sheng-Sheng Sun; Teng-Hao-Bo Deng; Ming Ao; Wen-Jun Yang; Xiao-Rui Liu; Ting Liu; Jian-Ming Zhu; Jean Louis Morel; Ye-Tao Tang; Rong-Liang Qiu (Geochimica et Cosmochimica Acta, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

The lncRNA20718-miR6022-RLPs module regulates tomato resistance to Phytophthora infestans - Jia-hui Zhang; Hong-bo Wei; Yu-hui Hong; Rui-rui Yang; Jun Meng; Yu-shi Luan (Plant Cell Reports, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Assessment for the data processing performance of non-target screening analysis based on high-resolution mass spectrometry - He Liu; Rui Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Enhancing physiological recovery and subsequent exercise performance in the heat using a phase-change material cooling blanket - Xin Wang; Bin Lai; Rui Yan; Yan Li; Bo Ning; Qian Wang (Journal of Thermal Biology, 2024)

Digital economy, structural deviation, and regional carbon emissions - Bo Xie; Rui Liu; Rajeev Dwivedi (Journal of Cleaner Production, 2024)

Study on barrier mechanism and application of silico-alkaline sol-modified bentonite cutoff wall materials to lead pollution in lead-zinc tailings pond - Rui Zhu; Changwen Ye; Bo Yu; Weiming Tao; Zhidong Zhou; Jie Li (Journal of Contaminant Hydrology, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Micro-nano bubble water with potassium fertigation improves strawberry yield and quality by changing soil bacterial community - Jian Wang; Qiu He; Kai Cao; Bo Zhou; Xiaoli Niu; Duo Wang; Rui Chen; Zhen Zheng (Rhizosphere, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Volatile organic compounds during routine production and planned shutdown of a petrochemical refinery: Emission characteristics, source and risk assessment - Yunxia Feng; Guolong Wang; Rui Dong; Bo Li; Dewu Ding; Jinchan Peng; Anshan Xiao (Atmospheric Pollution Research, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

Tracing nitrate pollution sources of karst groundwater in water resources using environmental isotopes - Yunfeng Zhang; Dalu Yu; Di Wu; Yuhui Zhao; Zhe Zhang; Bo Li; Baohui Huang; Mingguo Wang; Junru Gao; Yuxiao Kang; Rui Liu (Carbonates and Evaporites, 2023)

Rapid LC-MS/MS detection of 25-hydroxyvitamin D in dried blood spots - Hai-Bo Wang; Xuan Xiao; Wen Dai; Rui Peng; Juan Le; Yu-Qi Feng; Shao-Ting Wang (Analytica Chimica Acta, 2023)

Natural ocean iron fertilization and climate variability over geological periods - Hai‐Bo Jiang; David A. Hutchins; Wentao Ma; Rui‐Feng Zhang; Mark Wells; Nianzhi Jiao; Yuntao Wang; Fei Chai (Global Change Biology, 2023)
Marine primary producers are largely dependent on and shape the Earth's climate, although their relationship with climate varies over space and time. The growth of phytoplankton and associated marine primary productivity in most of the modern global ocean is limited by the supply of nutrients, including the micronutrient iron. The addition of iron via episodic and frequent events drives the biological carbon pump and promotes the sequestration of atmospheric carbon dioxide (CO 2 ) into the ocean. However, the dependence between iron and marine primary producers adaptively changes over different geological periods due to the variation in global climate and environment. In this review, we examined the role and importance of iron in modulating marine primary production during some specific geological periods, that is, the Great Oxidation Event (GOE) during the Huronian glaciation, the Snowball Earth Event during the Cryogenian, the glacial–interglacial cycles during the Pleistocene, and the period from the last glacial maximum to the late Holocene. Only the change trend of iron bioavailability and climate in the glacial–interglacial cycles is consistent with the Iron Hypothesis. During the GOE and the Snowball Earth periods, although the bioavailability of iron in the ocean and the climate changed dramatically, the changing trend of many factors contradicted the Iron Hypothesis. By detangling the relationship among marine primary productivity, iron availability and oceanic environments in different geological periods, this review can offer some new insights for evaluating the impact of ocean iron fertilization on removing CO 2 from the atmosphere and regulating the climate.

Toward the development of smart capabilities for understanding seafloor stretching morphology and biogeographic patterns via DenseNet from high-resolution multibeam bathymetric surveys for underwater vehicles - Rui Nian; Shasha Liu; Zongcan Lu; Xiaoyu Li; Shidong Ren; Yuqi Qian; Qiuying Li; Guotong He; Kexin Shi; Guoyao Zhang; Lina Zang; Luyao Li; et al. (Frontiers in Marine Science, 2023)
The increasing use of underwater vehicles facilitates deep-sea exploration at a wide range of depths and spatial scales. In this paper, we make an initial attempt to develop online computing strategies to identify seafloor categories and predict biogeographic patterns with a deep learning-based architecture, DenseNet, integrated with joint morphological cues, with the expectation of potentially developing its embedded smart capacities. We utilized high-resolution multibeam bathymetric measurements derived from MBES and denoted a collection of joint morphological cues to help with semantic mapping and localization. We systematically strengthened dominant feature propagation and promoted feature reuse via DenseNet by applying the channel attention module and spatial pyramid pooling. From our experiment results, the seafloor classification accuracy reached up to 89.87%, 82.01%, and 73.52% on average in terms of PA, MPA, and MIoU metrics, achieving comparable performances with the state-of-the-art deep learning frameworks. We made a preliminary study on potential biogeographic distribution statistics, which allowed us to delicately distinguish the functionality of probable submarine benthic habitats. This study demonstrates the premise of using underwater vehicles through unbiased means or pre-programmed path planning to quantify and estimate seafloor categories and the exhibited fine-scale biogeographic patterns.

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Unraveling heterogeneity of dissolved organic matter in highly connected natural water bodies at molecular level - Guan-Lin Chen; Chen Qian; Bo Gong; Meng Du; Rui-Zhe Sun; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

Straw bale construction towards nearly-zero energy building design with low carbon emission in northern China - Rui Bo; Hongrui Zhang; Zixuan Ma; Riyong Yin; An Li; Xunzhi Yin (Energy and Buildings, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Manipulation of crystallization nucleation and thermal degradation of PLA films by multi-morphologies CNC-ZnO nanoparticles - Ya-Fang Yan; Xiao-Bo Liang; Yan-Long Feng; Lin-Fang Shi; Rui-Pin Chen; Jian-Zhong Guo; Ying Guan (Carbohydrate Polymers, 2023)

Endophytic Fungus Talaromyces sp. MR1 Promotes the Growth and Cadmium Uptake of Arabidopsis thaliana L. Under Cadmium Stress - Yunhua Xiao; Rui Chen; Liang Chen; Bo Yang; Lihong Jiang; Jun Fang (Current Microbiology, 2023)

Discrete element-based regression analysis of initial ground stress and application to an extra-long tunnel in China - Ming-Rui Luo; Cheng-You Zhang; Bo Wang; Yan-Hua Zeng (Bulletin of Engineering Geology and the Environment, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Hydrogeological controls on chromium enrichment along the groundwater flow path in the Baiyangdian Catchment, North China Plain - Chao Liu; Huaming Guo; Wendi Fan; Rui Xu; Shuangbao Han; Bingying Gao; Bo Zhao; Chunping Jiang (Science of The Total Environment, 2023)

Analysis of the contribution of land consolidation to sustainable poverty alleviation under various natural conditions - Hanbing Li; Xiaobin Jin; Barbara Prack McCormick; Pablo Tittonell; Jing Liu; Bo Han; Rui Sun; Yinkang Zhou (Land Use Policy, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Polarity-extended liquid chromatography-triple quadrupole mass spectrometry for simultaneous hydrophilic and hydrophobic metabolite analysis - Rui Guo; Qisheng Zhong; Jiaqi Liu; Peiming Bai; Zongpeng Wang; Jieling Kou; Peijie Chen; Jie Zhang; Bo Zhang (Analytica Chimica Acta, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

Integrating data dependent and data independent non-target screening methods for monitoring emerging contaminants in the Pearl River of Guangdong Province, China - Rui Wang; Yanan Yan; He Liu; Yanxi Li; Meng Jin; Yuqing Li; RiZhu Tao; Qianghua Chen; Xuguang Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Understanding land-use sustainability with a systematical framework: An evaluation case of China - Bo Han; Xiaobin Jin; Rui Sun; Hanbing Li; Xinyuan Liang; Yinkang Zhou (Land Use Policy, 2023)

Variation, Determinants and prediction of carbon emissions in Guizhou, a new economic growth pole in southwest China - Lu Jiao; Rui Yang; Bo Chen; Yinling Zhang (Journal of Cleaner Production, 2023)

Characteristics of annual NH3 emissions from a conventional vegetable field under various nitrogen management strategies - Yan Wang; Zhisheng Yao; Yanqiang Wang; Guangxuan Yan; Baldur Janz; Xiaogang Wang; Yang Zhan; Rui Wang; Xunhua Zheng; Minghua Zhou; Bo Zhu; Ralf Kiese; et al. (Journal of Environmental Management, 2023)

Vegetation descriptors from Sentinel-1 SAR data for crop growth monitoring - Xin Bao; Rui Zhang; Jichao Lv; Renzhe Wu; Hongsheng Zhang; Jie Chen; Bo Zhang; Xiaoying Ouyang; Guoxiang Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Emission factors of ozone-depleting chloromethanes during production processes based on field measurements surrounding a typical chloromethane plant in China - Bowei Li; Xingchen Zhao; Xinhe Li; Xiaoyi Hu; Liting Hu; Di Chen; Minde An; Yang Yang; Rui Feng; Liya Guo; Pengnan Jiang; Bo Yao; et al. (Journal of Cleaner Production, 2023)

Spatiotemporal clustering analysis of shared electric vehicles based on trajectory data for sustainable urban governance - Lewen Bao; Zonglin Liu; Rui Miao; Zhihua Chen; Bo Zhang; Peng Guo; Yuze Ma (Journal of Cleaner Production, 2023)

Formation of giant copper deposits in Tibet driven by tearing of the subducted Indian plate - Zengqian Hou; Rui Wang; Haijiang Zhang; Yuanchuan Zheng; Sheng Jin; Hans Thybo; Roberto F. Weinberg; Bo Xu; Zhiming Yang; Ao-Wei Hao; Lei Gao; Letian Zhang (Earth-Science Reviews, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

The interference between effects of PFAS exposure on thyroid hormone disorders and cholesterol levels: an NHANES analysis - Liang Zheng; Zhecun Wang; Rui Yang; Wanna Chen; Jing Zhang; Ruixia Li; Weiming Lv; Bo Lin; Jiajun Luo (Environmental Science and Pollution Research, 2023)

Eastward extension of the Solonker Suture beneath the central Songliao Basin, NE China: Evidence from a deep seismic reflection profile - Ming-Rui Li; Rui Gao; Jian-Bo Zhou; Simon A Wilde; He-Sheng Hou; Xiao-Fan Deng (Gondwana Research, 2023)

Soil variables and reflected light revealed the plasticity of grape and wine composition: Regulation of the flavoromics under inner row gravel covering - Meng-Bo Tian; Wan-Hui Ma; Nong-Yu Xia; Jing Peng; Rui-Qi Hu; Chang-Qing Duan; Fei He (Food Chemistry, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Monetary evaluation of the external benefits of urban underground logistics System: A case study of Beijing - Xinwei Pan; Jianjun Dong; Rui Ren; Yicun Chen; Bo Sun; Zhilong Chen (Tunnelling and Underground Space Technology, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Geographic variation of litter chemistry and palatability in an invasive plant versus its native competitor - Yaolin Guo; Youzheng Zhang; Jihua Wu; Christina L. Richards; Oliver Bossdorf; Bo Li; Rui‐Ting Ju (Journal of Biogeography, 2023)
Aim Latitudinal variation in biotic interactions is recognized as a driver underlying variation in plant invasion success and therefore an important issue in conservation biogeography. However, previous studies have mainly focused on interactions between living plants and herbivores, whereas litter traits and detritivory have been hardly studied along latitude or compared between native and invasive plants. Our aim was to compare latitudinal variation in leaf litter chemistry and palatability to detritivores between invasive and native plants, and investigate which chemical traits determine detritivory and whether they are climate‐driven. Location China. Taxa Spartina alterniflora , Phragmites australis , Porcellio laevis , Chiromantes dehaani . Methods We combined field surveys with laboratory experiments to compare latitudinal variation in litter chemistry between the widespread invasive Spartina alterniflora and its native competitor Phragmites australis across their co‐occurring range (20.9–40.7° N, ~2200 km). For both species, we examined litter palatability to two common detritivores ( Porcellio laevis and Chiromantes dehaani ) along the same latitude. We also analysed relationships among climate, litter traits and detritivory. Results In five of nine litter traits, we found latitudinal clines, with little difference between the two plant species in how they responded across the gradient. Litter palatability decreased with increasing latitude, but was generally higher in Spartina than Phragmites . Two key litter traits (C:P ratio and flavonoid content) were significantly associated with temperature of origin and with detritivory. Main Conclusions There were geographic clines in litter traits and palatability, with strong links between climate, litter chemistry and detritivory, in both Spartina and Phragmites . Spartina litter, however, was more rapidly decomposed by detritivores, which could create positive feedbacks, and contributes to the successful Spartina invasion along China's coast. Future ecological restoration projects should therefore dispose Spartina plant tissue or litter off‐site, to reduce the competitiveness of Spartina and support the conservation of native Phragmites .

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

Subassembly Partition of Hull Block Based on Two-Dimensional PSO Algorithm - Bo Liu; Rui Li; Ji Wang; Yujun Liu; Sheng Li (Journal of Marine Science and Engineering, 2023)
Subassembly partition is an important process in hull block building as it greatly affects the efficiency and quality of the assembly work. Recently, an experience-based method has been widely applied to the subassembly partition process, which consumes much design time and manpower, thus causing more challenges toward a more highly automated and efficient stage in this process. To shorten the gap, an automated subassembly partition method is presented in this study. First, the assembly information model is defined with essential attributes and topological relations of the parts. Second, an optimization model is established with consideration of a trade-off between the intra-cluster cohesion and cluster number on the premise of satisfying certain constraints. After that, considering the fuzziness and diversity of the subassembly partition problem, a two-dimensional coding discrete particle swarm optimization (PSO) algorithm is developed. Finally, two blocks are demonstrated as instances to verify the proposed method, and the results show that the proposed method is feasible and applicable to the block with a flat structure.

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Spatiotemporal analysis of bike mobility chain: A new perspective on mobility pattern discovery in urban bike-sharing system - Rui Xin; Jian Yang; Bo Ai; Linfang Ding; Tingting Li; Ruoxin Zhu (Journal of Transport Geography, 2023)

Mechanisms of lithium selection from mixed LiCl-NaCl solution by nanopores: The synergistic effects of nanoconfinement and electric fields - Gang Liao; Xing-Yi Yue; Shi-Qi Zheng; Rui-Tian Ma; Hai-Bo Yi (Desalination, 2023)

Identification of the chemical constituents in Cullen corylifolium ethanolic extract by LC-MS/MS and GC-MS - Hongzheng Wang; Keyu Chen; Rui Xue; Chimengul Turghun; Bo Han (Natural Product Research, 2023)

Post COVID-19 pandemic recovery of intracity human mobility in Wuhan: Spatiotemporal characteristic and driving mechanism - Rui An; Zhaomin Tong; Xiaoyan Liu; Bo Tan; Qiangqiang Xiong; Huixin Pang; Yaolin Liu; Gang Xu (Travel Behaviour and Society, 2023)

Bibenzyls and lignans from Dendrobium devonianum and their immunosuppressive activities - Jinyu Li; Xinyue Zhang; Yumeng Li; Bo Liu; Rui Zhan (Phytochemistry Letters, 2023)

Origin of biotite-rich xenoliths in the Eocene Beiya porphyry: Implications for upper-crustal Au remobilization and formation of giant porphyry Au systems in a collisional setting - Ye Zhou; Zengqian Hou; Rui Wang; Bo Xu; Noreen J. Evans; Wenyan He; Yuanchuan Zheng; Jiaxi Zhou (Lithos, 2023)

Apatite and fluorite control the transport of tungsten in calcium-bearing hydrothermal fluids - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Zi-Qi Jiang; Lin-Bo Shang; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2023)

NAT10 accelerates pulmonary fibrosis through N4-acetylated TGFB1-initiated epithelial-to-mesenchymal transition upon ambient fine particulate matter exposure - Shenshen Wu; Lijia Yin; Ke Han; Bo Jiang; Qingtao Meng; Michael Aschner; Xiaobo Li; Rui Chen (Environmental Pollution, 2023)

Determination of Rock Mass Parameters for the RHT Model Based on the Hoek–Brown Criterion - Shenglin Li; Tianlong Ling; Dianshu Liu; Shufeng Liang; Rui Zhang; Bo Huang; Kai Liu (Rock Mechanics and Rock Engineering, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Formulation improvement of a concentrated enzyme detergent for high-speed rail trains through life cycle assessment methodology - Changyan Yang; Yu Gong; Yinhang Qu; Jiayi Li; Bohan Yang; Rui Li; Dorothy S. Zhang; Baowei Wang; Yigang Ding; Bo Zhang (Environment, Development and Sustainability, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Numerical simulations and optimized design on the performance and thermal stress of a thermoelectric cooler - Jingshuang Zhang; Huadong Zhao; Bo Feng; Xiaohui Song; Xiang Zhang; Rui Zhang (International Journal of Refrigeration, 2023)

Characteristics and intrinsic influencing factors of log humification depend on wood traits in a subalpine forest - Zhuang Wang; Qin Wang; Bo Tan; Chenhui Chang; Lifeng Wang; Rui Cao; Yurui Jang; Jörg Müller; Wanqin Yang (CATENA, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Snow depth variability across the Qinghai Plateau and its influencing factors during 1980–2018 - Heng Ma; Gangfeng Zhang; Rui Mao; Bo Su; Weihang Liu; Peijun Shi (International Journal of Climatology, 2023)
As a crucial component of the climate system, snow cover plays an important role on surface energy budgets, hydrological cycles and socioeconomic development. This paper investigated the spatiotemporal patterns of snow depth across the Qinghai Plateau (QP) during 1980–2018 based on passive microwave (PMW) satellite observation and reanalysis products. The study identified the relationships between the changes in PMW snow depth and topographic features and revealed the impact of climatic variables (air temperature, precipitation and wind speed) and large‐scale atmospheric circulations on observed snow depth variability. The results show that the spatial pattern of snow depth climatology is similar in all datasets, except in terms of magnitude, with high values in the southern and southeastern parts of the QP and low values in the eastern and northwestern parts. Average snow depth correlates positively with precipitation, elevation and slope, and negatively with air temperature and wind speed. The long‐term trends in snow depth vary with the season and the datasets. The PMW snow depth across the QP shows a significant annual (−0.125 cm·decades −1 , p −1 , p

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Branch development in monoculture and mixed-species plantations of Betula alnoides, Erythrophleum fordii and Pinus kesiya var. langbianensis in southwestern China - Kai-Li Liu; Chun-Sheng Wang; Bo-Yao Chen; Rui-Hui Wang; Jie Zeng (Forest Ecology and Management, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

Patternable thermal conductive interface materials enabled by vitrimeric phase change materials - Li-Mei Peng; Zhao Xu; Jie Yang; Lu Bai; Rui-Ying Bao; Ming-Bo Yang; Wei Yang (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Graphene electrochemical transistor incorporated with gel electrolyte for wearable and non-invasive glucose monitoring - Nan Gao; Rui Zhou; Bo Tu; Tian Tao; Yongqiao Song; Zhiwei Cai; Hanping He; Gang Chang; Yuxiang Wu; Yunbin He (Analytica Chimica Acta, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Overexpression of α-Tubulin Gene of Sugarcane (Saccharum spp. hybrids), SoTUA, Enhances Tobacco Tolerance to Cold Stress - Jiao-Yun Chen; Bo Sun; Qaisar Khan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Effects and mechanism of ultrasound treatment on Chironomus kiiensis eggs - Bo-dong Liu; Hao-tao Dong; Hong-wei Rong; Rui-jian Zhang (Environmental Science and Pollution Research, 2022)

Effects of snow absence on available N pools and enzyme activities within soil aggregates in a spruce forest on the eastern Tibetan Plateau - Zhijie Li; Rüdiger Reichel; Zimin Li; Kaijun Yang; Li Zhang; Bo Tan; Rui Yin; Kerui Zhao; Zhenfeng Xu (Soil Ecology Letters, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Clinical Reference Strategy for the Selection of Treatment Materials for Maxillofacial Bone Transplantation: A Systematic Review and Network Meta-Analysis - Shuxin Zhang; Xinyi Zhang; Yanli Li; Xuran Mao; Rui Liu; Yanxin Qi; Eui-Seok Lee; Heng Bo Jiang (Tissue Engineering and Regenerative Medicine, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

China’s food security situation and key questions in the new era: A perspective of farmland protection - Xinyuan Liang; Xiaobin Jin; Bo Han; Rui Sun; Weiyi Xu; Hanbing Li; Jie He; Jin Li (Journal of Geographical Sciences, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Experimental study on the mechanical properties and energy evolution of hard rock during water immersion - Fan-Bo Wei; Bing-Rui Chen; Rui Wang; Guo-Liang Li; Tao Li; Xu Wang; Xin-Hao Zhu (Arabian Journal of Geosciences, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Development of sustainable self-compacting concrete using recycled concrete aggregate and fly ash, slag, silica fume - Zhanggen Guo; Jing Zhang; Tao Jiang; Tianxun Jiang; Chen Chen; Rui Bo; Yan Sun (European Journal of Environmental and Civil Engineering, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Responses of estuarine circulation to the morphological evolution in a convergent, microtidal estuary - Rui Zhang; Bo Hong; Lei Zhu; Wenping Gong; Heng Zhang (Ocean Science, 2022)
The Huangmaohai estuary (HE) is a funnel-shaped microtidal estuary in the west of the Pearl River Delta (PRD) in southern China. Since China reformed and opened up in 1978, extensive human activities have occurred and greatly changed the estuary's topography and modified its hydrodynamics. In this study, we examined the morphological evolution by analyzing remote sensing data with ArcGIS tools and studied the responses of hydrodynamics to the changes in topography from 1977 to 2010 by using the Delft3D model. We took the changes in estuarine circulation during neap tides in dry seasons as an example. The results show that human reclamation caused a narrowing of the estuary, and channel dredging deepened the estuary. These human activities changed both the longitudinal and lateral estuarine circulations. The longitudinal circulation was observed to increase with the deepening and narrowing of the estuary. The lateral circulation experienced changes in both the magnitude and pattern. The momentum balance analysis shows that when the depth and width changed simultaneously, the longitudinal estuarine circulation was modulated by both the channel deepening and width reduction, in which the friction, pressure gradient force, and advection terms were altered. The analysis of the longitudinal vortex dynamics indicates that the changes in the vertical shear of the longitudinal flow, lateral salinity gradient, and vertical mixing were responsible for the change in the lateral circulation. The changes in water depth are the dominant factors affecting lateral circulation intensity. This study has implications for sediment transport and morphological evolution in estuaries heavily impacted by human interventions.

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

The responses of detoxification enzyme and gene expression in western flower thrips, Frankliniella occidentalis, to new challenging hosts - Wen-Bo Yue; Jun-Rui Zhi; Li Liu; Xiao-Lin Hou; Mao Ye (Arthropod-Plant Interactions, 2022)

The Identification and Prediction of Mesoscale Eddy Variation via Memory in Memory With Scheduled Sampling for Sea Level Anomaly - Rui Nian; Yu Cai; Zhengguang Zhang; Hui He; Jingyu Wu; Qiang Yuan; Xue Geng; Yuqi Qian; Hua Yang; Bo He (Frontiers in Marine Science, 2021)
Ocean mesoscale eddies are ubiquitous in world ocean and account for 90% oceanic kinetic energy, which dominate the upper ocean flow field. Accurately predicting the variation of ocean mesoscale eddies is the key to understand the oceanic flow field and circulation system. In this article, we propose to make an initial attempt to explore spatio-temporal predictability of mesoscale eddies, employing deep learning architecture, which primarily establishes Memory In Memory (MIM) for sea level anomaly (SLA) prediction, combined with the existing mesoscale eddy detection. Oriented to the western Pacific ocean (125°−137.5°E and 15°−27.5°N), we quantitatively investigate the historic daily SLA variability at a 0.25° spatial resolution from 2000 to 2018, derived by satellite altimetry. We develop the enhanced MIM prediction strategies, equipped with Gated Recurrent Unit (GRU) and spatial attention module, in a scheduled sampling manner, which overcomes the gradient vanishing and complements to strengthen spatio-temporal features for long-term dependencies. At the early stage, the real value SLA input guides the model training process for initialization, while the scheduled sampling intentionally feeds the newly predicted value, to resolve the distribution inconsistency of inference. It has been demonstrated in our experiment results that our proposed prediction scheme outperformed the state-of-art approaches for SLA time series, with MAPE, RMSE of the 14-day prediction duration, respectively, 5.1%, 0.023 m on average, even up to 4.6%, 0.018 m for the effective sub-regions, compared to 19.8%, 0.086 m in ConvLSTM and 8.3%, 0.040 m in original MIM, which greatly facilitated the mesoscale eddy prediction. This proposed scheme will be beneficial to understand of the underlying dynamical mechanism behind the predictability of mesoscale eddies in the future, and help the deployment of ARGO, glider, AUV and other observational platforms.

Carbonaceous nanoparticles in Zibo hot springs: Implications for the cycling of carbon and associated elements - Xiaobo Tan; Benyu Bo; Peng Zhang; Guangyu Shao; Rui Liu; Kun Wang (Environmental Chemistry Letters, 2021)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Microseismic source location method based on a velocity model database and statistical analysis - Bing-Rui Chen; Tao Li; Xin-Hao Zhu; Fan-Bo Wei; Xu Wang; Ming-Xing Xie (Arabian Journal of Geosciences, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Bo Tan; Rui Yin; Jian Zhang; Zhenfeng Xu; Yang Liu; Shuqin He; Li Zhang; Han Li; Lixia Wang; Sining Liu; Chengming You; Changhui Peng (Ecosystems, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

The Identification and Prediction in Abundance Variation of Atlantic Cod via Long Short-Term Memory With Periodicity, Time–Frequency Co-movement, and Lead-Lag Effect Across Sea Surface Temperature, Sea Surface Salinity, Catches, and Prey Biomass From 1919 to 2016 - Rui Nian; Qiang Yuan; Hui He; Xue Geng; Chi-Wei Su; Bo He; Amaury Lendasse (Frontiers in Marine Science, 2021)
The population of Atlantic cod significantly contributes to the prosperity of fishery production in the world. In this paper, we quantitatively investigate the global abundance variation in Atlantic cod from 1919 to 2016, in favor of spatiotemporal interactions over manifold impact factors at local observation sites, and propose to explore the predictive mechanism with the help of its periodicity, time–frequency co-movement, and lead-lag effects, via long short-term memory (LSTM). We first integrate evidences yielded from wavelet coefficients, to suggest that the abundance variation potentially follows a 36-year major cycle and 24-year secondary cycle at the time scales of 55 years and 37 years. We further evaluate the responses of Atlantic cod abundance to the external impact factors, including sea surface temperature (SST), catches, prey biomass, and sea surface salinity (SSS), in aid of the wavelet coherence and phase difference, which allows us to identify the dominantly correlative factors and capture the leading roles along the time domain and then divide the responses around the recent 60 years into three stages: before 1985, 1985–1995, and after 1995. At the first stage, the reason for the decline in abundance could be mainly attributed to the rapid rise of fish catches. At the second stage, the impact of SST and SSS also provides significant indices, besides overfishing; meanwhile, the mortality of primary producers and forced migration of fish species indirectly cause the decline. At the third stage, warming SST and growing SSS directly led to the decrease of abundance. Finally, we establish one ensemble of LSTM-SAE architecture to comprehensively reflect the predictive patterns at each stage. It has been demonstrated from experimental results that the models behaved better when intentionally feeding with the dominantly correlative multivariate inputs, instead of either all factors or only the abundance. The proposed scheme provides opportunities to symmetrically identify the underlying predictive attributes of Atlantic cod abundance and potentially perform as the quantitative references in reasonably making fishing decision. With the rapid development in deep learning capabilities, it is hopeful to expect better predictions of the responses to global changes, not only for Atlantic cod but also for other fish species and the ecosystem as a whole.

Catalytic Hydroprocessing of White Pine Pyrolysis Bio-Oil over Cobalt-Molybdenum Carbide in a Continuous Packed-Bed Reactor - Rui Li; Zhixin Zhao; Bo Zhang; Xiaozheng Sun; Zhen Zhang; Ying Zhang; Haitao Chen; Qiangu Yan (BioEnergy Research, 2021)

An IPSO-RNN machine learning model for soil landslide displacement prediction - Tao Zheng; Qi hua Zhao; Jian bo Hu; Jun feng Jiang; Rui Su (Arabian Journal of Geosciences, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Diarylpropanes from Horsfieldia kingii - Bo Liu; Ye-Gao Chen; Xing-Jun Tian; Rui Zhan (Natural Product Research, 2021)

Arbuscular mycorrhizal fungus-induced decrease in nitrogen concentration in pore water and nitrogen leaching loss from red soil under simulated heavy rainfall - Yongmei He; Bo Li; Kai Yan; Rui Yang; Gang Lei; Mingrui Li; Yuan Li; Fangdong Zhan (Environmental Science and Pollution Research, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Research on the Bearing Capacity of a Damaged Jacket Repaired by a Grouting Clamp Based on a Type of Wedge Gripping - Bo Zhang; Qing Rui Zhang; Tao Wang; Zhuo Wang (Journal of Marine Science and Engineering, 2020)
In the process of repairing a damaged jacket with a grouting clamp, it is necessary to analyze the bearing capacity of the damaged structure to determine whether it meets requirements for maintenance and reinforcement. On the basis of previous research results, this paper proposes a design scheme of a grouting clamp based on wedge gripping, which can effectively improve the local bearing capacity of the jacket by more than 35%. The elastic–plastic theory was used to analyze the bearing capacities of steel pipe piles under three different conditions (ideal steel pipe, bending steel pipe and steel pipe with a defective section) and with reinforcement by a grouting hoop. The bearing capacity of the mechanical grouting clamp was analyzed, and the resulting theoretical design was verified by a bearing performance experiment. The results support the conclusion that the wedge mechanical grouting clamp can effectively strengthen local jacket members.

Risk assessment of lead intake via food among residents in the mining areas of Nandan County, China - Yunxia Zhang; Bo Song; Rui Pang; Lang Zhou (Environmental Geochemistry and Health, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Surface fractal dimensions as a characterization parameter for methane adsorption–induced coal strains - Jie Zhu; Yang Zhang; Rui Zhang; Bo Zhang; Jun Tang; Fa He (Arabian Journal of Geosciences, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

Utilizing borehole electrical images to evaluate sorting of conglomeratic formation: example from Lower Triassic Baikouquan Formation in Well M152, Mahu Depression, Junggar Basin, China - Rui Yuan; Bo Yang; Lingyu Huang; Wei Hu (Arabian Journal of Geosciences, 2020)

Causes and Treatment Measures of Submarine Pipeline Free-Spanning - Bo Zhang; Rui Gong; Tao Wang; Zhuo Wang (Journal of Marine Science and Engineering, 2020)
Submarine pipelines, as arteries for offshore oil and gas transportation, play a particularly important role in the exploitation of offshore oil and gas resources. Since the world’s first submarine pipelines were laid in the Gulf of Mexico, numerous failures have been caused by pipeline free-spanning. This paper provides a review of the causes and treatment measures for the free span of submarine pipeline. Various factors cause the free span of submarine pipelines, including wave flow scouring, fluctuations in seabed topography, residual stress or thermal stress of pipelines, and human activities. The scour of the wave current is the main factor affecting free span; the research on sediment starting and equilibrium depth during scour is reviewed in-depth. For the span treatment of submarine pipelines, the main measures available at present include the re-digging trench burying, structural support, covering bionic water plants, and choke plate self-burying. For each, the principle, advantages, disadvantages, and research are discussed. This review provides a convenient resource for understanding the causes of submarine free-spanning pipelines and choosing suitable treatment measures.

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Temporal variations in riverine hydrochemistry and estimation of the carbon sink produced by coupled carbonate weathering with aquatic photosynthesis on land: an example from the Xijiang River, a large subtropical karst-dominated river in China - Rui Yang; Hailong Sun; Bo Chen; Mingxing Yang; Qingrui Zeng; Cheng Zeng; Jie Huang; Huixian Luo; Danhui Lin (Environmental Science and Pollution Research, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Forest gaps retard carbon and nutrient release from twig litter in alpine forest ecosystems - Bo Tan; Jian Zhang; Wanqin Yang; Rui Yin; Zhenfeng Xu; Yang Liu; Li Zhang; Han Li; Chengming You (European Journal of Forest Research, 2020)

Utilizing Gompertz curve to calculate median, mean and sorting of grain-size distribution (GSD) - Rui Yuan; Bo Yang (Arabian Journal of Geosciences, 2020)

Long-term In Situ Permeability Variations of an Active Fault Zone in the Interseismic Period - Yuchuan Ma; Guangcai Wang; Rui Yan; Bo Wang (Pure and Applied Geophysics, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Evaluation of Liquefaction Potential in Saturated Sand under Different Drainage Boundary Conditions—An Energy Approach - Chang-Rui Yao; Bo Wang; Zhi-Qiang Liu; Hao Fan; Fang-Hao Sun; Xin-Hao Chang (Journal of Marine Science and Engineering, 2019)
Drainage conditions are supposed to have significant influence on sand liquefaction behavior. An infiltration device was utilized in cyclic triaxial tests to reproduce different drainage conditions by altering dry density of the within silt. Permeability coefficient ratio (kp) was utilized for quantifying the drainage boundary effect. Cyclic triaxial tests were conducted on saturated Fujian standard sand samples. Test results were used to evaluate the liquefaction potential by using the energy approach. It can be concluded that, if kp increases slightly bigger than zero, excess pore water pressure (EPWP) will respond more fiercely, and the dissipated energy that triggers sand liquefaction will be less. By considering kp, an energy-based database was built by taking kp into consideration and different neural network (NN) models were constructed to predict liquefaction potential by energy approaches accurately under different drainage boundary conditions. It was suggested that the neuro-fuzzy (NF)-based NN model has more satisfactory performance.

Effects of Epixylic Vegetation Removal on the Dynamics of the Microbial Community Composition in Decaying Logs in an Alpine Forest - Chenhui Chang; Fuzhong Wu; Zhuang Wang; Bo Tan; Rui Cao; Wanqin Yang; Johannes H. C. Cornelissen (Ecosystems, 2019)

Two new sesquineolignans from the seeds of Crataegus pinnatifida and their β -amyloid aggregation inhibitory activitiy - Rui Guo; Le Zhou; Peng Zhao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Modeling the Mechanical Behavior of Gas Hydrate Bearing Sediments Based on Unified Hardening Framework - Kai Li; Rui-ming Liu; Liang Kong; Xin-bo Zhao (Geotechnical and Geological Engineering, 2019)

Effects of frequency and confining pressure on consolidation drainage behavior of soft marine clays - Yong-Hong Miao; Fan-Bo Zhou; Jie Yin; Yan-Chang Sun; Rui-Bing Li; Jian-Fei Lu (Marine Georesources & Geotechnology, 2019)

A new coumarin from Juglans mandshurica Maxim induce apoptosis in hepatocarcinoma cells - Li-Li Lou; Peng Zhao; Zhuo-Yang Cheng; Rui Guo; Guo-Dong Yao; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Reduced hemispheric asymmetry of brain anatomical networks in attention deficit hyperactivity disorder - Dandan Li; Ting Li; Yan Niu; Jie Xiang; Rui Cao; Bo Liu; Hui Zhang; Bin Wang (Brain Imaging and Behavior, 2019)

Oxidation of high iron content electroplating sludge in supercritical water: stabilization of zinc and chromium - Bo Zhang; Yinghui Wang; Xingying Tang; Shaopeng Wang; Chaoshuai Wei; Rui Wang; Wei Zhang (Environmental Science and Pollution Research, 2019)

An Innovative Sampling Method for Determining the Scale Effect of Rock Joints - Rui Yong; Ji-Bo Qin; Man Huang; Shi-Gui Du; Jie Liu; Gao-Jian Hu (Rock Mechanics and Rock Engineering, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

The role of lamin A/C in mesenchymal stem cell differentiation - Bo Zhang; Yang Yang; Reziwan Keyimu; Jin Hao; Zhihe Zhao; Rui Ye (Journal of Physiology and Biochemistry, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Two new lignans from Horsfieldia kingii - Bo Liu; Shou-Zhen Du; Fang Kuang; Ying Liu; Xing-Jun Tian; Ye-Gao Chen; Rui Zhan (Natural Product Research, 2019)

Inhibition of YAP with siRNA prevents cartilage degradation and ameliorates osteoarthritis development - Yong Gong; Song-Jian Li; Rui Liu; Jian-Feng Zhan; Chao Tan; Yi-Fei Fang; Yan Chen; Bo Yu (Journal of Molecular Medicine, 2019)

The role of autophagy in pulmonary hypertension: a double-edge sword - Rui Chen; Meiping Jiang; Bo Li; Wei Zhong; Zhongqun Wang; Wei Yuan; Jinchuan Yan (Apoptosis, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Increasing grassland degradation stimulates the non-growing season CO2 emissions from an alpine meadow on the Qinghai–Tibetan Plateau - Lei Ma; Zhisheng Yao; Xunhua Zheng; Han Zhang; Kai Wang; Bo Zhu; Rui Wang; Wei Zhang; Chunyan Liu (Environmental Science and Pollution Research, 2018)

Recent Developments in Commercial Processes for Refining Bio-Feedstocks to Renewable Diesel - Bo Zhang; Jinsheng Wu; Changyan Yang; Qi Qiu; Qiangu Yan; Rui Li; Baowei Wang; Jinlong Wu; Yigang Ding (BioEnergy Research, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

An Experimental Investigation of the Failure Mechanisms of Jointed and Intact Marble under Compression Based on Quantitative Analysis of Acoustic Emission Waveforms - Zheng-Hu Zhang; Jian-Hui Deng; Jian-Bo Zhu; Lin-Rui Li (Rock Mechanics and Rock Engineering, 2018)

The gravity field model IGGT_R1 based on the second invariant of the GOCE gravitational gradient tensor - Biao Lu; Zhicai Luo; Bo Zhong; Hao Zhou; Frank Flechtner; Christoph Förste; Franz Barthelmes; Rui Zhou (Journal of Geodesy, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

CD137–CD137L interaction modulates neointima formation and the phenotype transformation of vascular smooth muscle cells via NFATc1 signaling - Wei Zhong; Bo Li; Ping Yang; Rui Chen; Cuiping Wang; Zhongqun Wang; Chen Shao; Wei Yuan; Jinchuan Yan (Molecular and Cellular Biochemistry, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

The higher grain production, the more social deprivation? A case study of Henan province in traditional agricultural areas of China - Jun-bo Gao; Wei-feng Qiao; Yan-sui Liu; Yu-rui Li; Wei Tu; Yong-xian Zhang (Journal of Mountain Science, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Development and characterization of 32 SNP markers for the northern snakehead (Channa argus) using high resolution melting (HRM) - Bo-Chi Zhang; Gui-Rong Zhang; Wei Ji; Rui-Bin Yang; Gui-Wei Zou; Kun-Ci Chen; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics Resources, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Boron-bridged RG-II and calcium are required to maintain the pectin network of the Arabidopsis seed mucilage ultrastructure - Da-chuan Shi; Juan Wang; Rui-bo Hu; Gong-ke Zhou; Malcolm A. O’Neill; Ying-zhen Kong (Plant Molecular Biology, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Effects of Cold Stress on Root Growth and Physiological Metabolisms in Seedlings of Different Sugarcane Varieties - Bo Sun; Guang-Ling Liu; Thi Thu Phan; Li-Tao Yang; Yang-Rui Li; Yong-Xiu Xing (Sugar Tech, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

Blood Flow and Oxygen Transport in Descending Branch of Lateral Femoral Circumflex Arteries After Transfemoral Amputation: A Numerical Study - Fei Yan; Wen-Tao Jiang; Rui-Qi Dong; Qing-Yuan Wang; Yu-Bo Fan; Ming Zhang (Journal of Medical and Biological Engineering, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Investigating the Effect of Tissue Size on Mycelial Growth of Seven Mushroom Species by Using a Novel Device for Precise Tissue Isolation - Sheng-Rong Liu; Wei-Rui Zhang; Ai-Ping Chen; Yun-Bo Kuang (Indian Journal of Microbiology, 2016)

Adenovirus-mediated shRNA interference against HSV-1 replication in vitro - Bo Song; Xinjing Liu; Qingzhi Wang; Rui Zhang; Ting Yang; Zhiqiang Han; Yuming Xu (Journal of NeuroVirology, 2016)

Overexpression of sugarcane gene SoSnRK2.1 confers drought tolerance in transgenic tobacco - Thi-Thu Phan; Bo Sun; Jun-Qi Niu; Qin-Liang Tan; Jian Li; Li-Tao Yang; Yang-Rui Li (Plant Cell Reports, 2016)

Functional analysis of a chitinase gene during the larval-nymph transition in Panonychus citri by RNA interference - Wen-Kai Xia; Xiao-Min Shen; Tian-Bo Ding; Jin-Zhi Niu; Rui Zhong; Chong-Yu Liao; Ying-Cai Feng; Wei Dou; Jin-Jun Wang (Experimental and Applied Acarology, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

The extended phenology of Spartina invasion alters a native herbivorous insect’s abundance and diet in a Chinese salt marsh - Rui-Ting Ju; Yang-Yun Chen; Lei Gao; Bo Li (Biological Invasions, 2016)

Characterization of a NaCl-tolerant β-N-acetylglucosaminidase from Sphingobacterium sp. HWLB1 - Junpei Zhou; Zhifeng Song; Rui Zhang; Limei Ding; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

Phylogenetic analysis reveals that Japanese encephalitis virus genotype III is still prevalent in swine herds in Sichuan province in China - Rui Wu; Qiao Wang; Hongming Liu; Chunxia Chai; Bo He; Xiaobo Huang; Yiping Wen; Xintian Wen; Qiguai Yan; Xiaoping Ma; Sanjie Cao (Archives of Virology, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

Geological and geochronological constraints on the genesis of the giant Tongkuangyu Cu deposit (Palaeoproterozoic), North China Craton - Xuan Liu; Hong-Rui Fan; M. Santosh; Kui-Feng Yang; Zheng-Jie Qiu; Fang-Fang Hu; Bo-Jie Wen (International Geology Review, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Tempo-spatial analysis of water quality in tributary bays of the Three Gorges Reservoir region (China) - Jialiang Tang; Tao Wang; Bo Zhu; Pei Zhao; Yi Xiao; Rui Wang (Environmental Science and Pollution Research, 2015)

Changes in photosynthesis of alpine plant Saussurea superba during leaf expansion - Sheng-Bo Shi; Rui Shi; Miao Li (Acta Physiologiae Plantarum, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Tree‐ring reconstruction of July–May precipitation ( AD 1816–2010) in the northwestern marginal zone of the East Asian summer monsoon reveals the monsoon‐related climate signals - Feng Chen; Huiqin Wang; Fa‐hu Chen; Yujiang Yuan; Rui‐bo Zhang (International Journal of Climatology, 2015)
A July–May precipitation reconstruction for the period AD 1816–2010 was developed from a tree‐ring width chronology of Picea wilsonii for the Xinglong Mountains area of Lanzhou. The reconstruction explains 55.8% of the actual precipitation variance during the calibration period from 1951 to 2010. Wet conditions prevailed during the periods 1822–1835, 1843–1858, 1870–1877, 1884–1891, 1911–1921, 1933–1938, 1944–1979 and 2009–2010. Dry episodes occurred during 1816–1821, 1836–1842, 1859–1869, 1878–1883, 1892–1910, 1922–1932, 1939–1943 and 1980–2008. Multi‐taper method spectral analysis indicates the existence of some significant peaks at 2.8, 3.0 and 3.5 years. Spatial correlations with gridded land surface precipitation data revealed that our reconstruction represents regional precipitation signal for a large area of North China linked to the East Asian summer monsoon (EASM). Comparison with other tree‐ring‐based precipitation/drought reconstructions from surrounding areas implies a high degree of confidence for our reconstruction. Precipitation variations in the study area are significantly correlated with sea surface temperatures in eastern equatorial Pacific Ocean and tropical western Pacific Ocean, suggesting a possible connection of regional precipitation variations to the EASM and the El Niño‐Southern Oscillation (ENSO).

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

Recent climate warming of central China reflected by temperature-sensitive tree growth in the eastern Qinling Mountains and its linkages to the Pacific and Atlantic oceans - Feng Chen; Rui-bo Zhang; Hui-qin Wang; Li Qin (Journal of Mountain Science, 2015)

Characterization of Sphingomonas sp. JB13 exo-inulinase: a novel detergent-, salt-, and protease-tolerant exo-inulinase - Junpei Zhou; Mozhen Peng; Rui Zhang; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Yajie Gao; Junrong Ren; Zunxi Huang (Extremophiles, 2015)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

A new naphthol from the twigs and leaves of Pterospermum yunnanense - Haoliang Li; Guoli Huang; Bo Liu; Ying Liu; Rui Zhan; Yegao Chen (Natural Product Research, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Time-dependent damage constitutive model for the marble in the Jinping II hydropower station in China - Bing-Rui Chen; Xiao-Jun Zhao; Xia-Ting Feng; Hong-Bo Zhao; Shan-Yong Wang (Bulletin of Engineering Geology and the Environment, 2014)

Synthesis and antitumor activity evaluation of 2-arylisoquinoline-1,3(2H,4H)-diones in vitro and in vivo - Bo-Rui Kang; Juan Wang; Huan Li; Yan Li; Qi-Bing Mei; San-Qi Zhang (Medicinal Chemistry Research, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Origin of the Yinshan epithermal-porphyry Cu–Au–Pb–Zn–Ag deposit, southeastern China: insights from geochemistry, Sr–Nd and zircon U–Pb–Hf–O isotopes - Xuan Liu; Hong-Rui Fan; M. Santosh; Fang-Fang Hu; Kui-Feng Yang; Bo-Jie Wen; Yue-Heng Yang; Yongsheng Liu (International Geology Review, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Effect of total dissolved gas supersaturated water on early life of David’s schizothoracin (Schizothorax davidi) - Rui-feng Liang; Bo Li; Ke-feng Li; You-cai Tuo (Journal of Zhejiang University-SCIENCE B, 2013)

Complete disassociation of adult pancreas into viable single cells through cold trypsin-EDTA digestion - Dan Li; Shi-yun Peng; Zhen-wu Zhang; Rui-cheng Feng; Lu Li; Jie Liang; Sheng Tai; Chun-bo Teng (Journal of Zhejiang University-SCIENCE B, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Integrated application of 3D seismic and microseismic data in the development of tight gas reservoirs - Rui-Zhao Yang; Zheng-Guang Zhao; Wei-Jun Peng; Yu-Bo Gu; Zhan-Gang Wang; Xi-Qin Zhuang (Applied Geophysics, 2013)

Conservation genetics of the endangered terrestrial orchid Liparis japonica in Northeast China based on AFLP markers - Xuhui Chen; Junjie Guan; Rui Ding; Qun Zhang; Xingze Ling; Bo Qu; Lijun Zhang (Plant Systematics and Evolution, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Overexpression of a Transcription Factor OsMADS15 Modifies Plant Architecture and Flowering Time in Rice (Oryza sativa L.) - Sun-Jie Lu; He Wei; Ya Wang; Hui-Mei Wang; Rui-Fang Yang; Xiao-Bo Zhang; Ju-Min Tu (Plant Molecular Biology Reporter, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Historical and botanical evidence of distribution, cultivation and utilization of Linum usitatissimum L. (flax) in China - Fei-Hu Liu; Xia Chen; Bo Long; Rui-Yan Shuai; Chun-Lin Long (Vegetation History and Archaeobotany, 2011)

Age-dependent expression of forkhead box O proteins in the duodenum of rats - Pan Huang; Zhen-qi Zhou; Rui-hua Huang; Bo Zhou; Quan-wei Wei; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2011)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

Assessment of spatial distribution of soil loss over the upper basin of Miyun reservoir in China based on RS and GIS techniques - Tao Chen; Rui-qing Niu; Yi Wang; Ping-xiang Li; Liang-pei Zhang; Bo Du (Environmental Monitoring and Assessment, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Effect of host plants on development and reproduction of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Rui-Ting Ju; Feng Wang; Fang-Hao Wan; Bo Li (Journal of Pest Science, 2011)

Multiple induced mutagenesis for improvement of ethanol production by Kluyveromyces marxianus - Zong-wen Pang; Jing-juan Liang; Xiao-juan Qin; Ji-rui Wang; Jia-xun Feng; Ri-bo Huang (Biotechnology Letters, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

The promotion of clean development mechanism to cement industry capturing waste heat for power generation in China - Qishe Yan; Chang-Bo Zhou; Peng Qu; Rui-qin Zhang (Mitigation and Adaptation Strategies for Global Change, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Genome-wide Comparisons of Gene Expression for Yield Heterosis in Maize - Bo Li; Deng-Feng Zhang; Guan-Qing Jia; Jing-Rui Dai; Shou-Cai Wang (Plant Molecular Biology Reporter, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

High level expression of a functional human/mouse chimeric anti-CD20 monoclonal antibody in milk of transgenic mice - Bo Tang; Shanshan Yu; Min Zheng; Fangrong Ding; Rui Zhao; Jianmin Zhao; Yunping Dai; Ning Li (Transgenic Research, 2008)

Endogenous KV channels in human embryonic kidney (HEK-293) cells - Bo Jiang; Xianfeng Sun; Kun Cao; Rui Wang (Molecular and Cellular Biochemistry, 2002)